Rare earth permanent magnet, preparation method thereof and motor
By designing core-shell structure and graphene dispersion in rare earth permanent magnets, combining magnetic field orientation pressing and hot pressing processes, the balance problem of rare earth permanent magnets between magnetic properties and mechanical properties is solved, and high coercivity and durability are achieved. Improvement of flexural strength.
Patent Information
- Application Number
- CN202310694307.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-12
AI Technical Summary
Rare earth permanent magnets are difficult to achieve high coercive force, high durability and high bending strength at the same time, and the existing methods have not improved the mechanical properties when improving magnetic properties.
A rare earth permanent magnet is adopted, which includes the main phase and the grain boundary phase. The main phase is dispersed in the grain boundary phase. The main phase is a core-shell structure. The shell and the grain boundary phase contain graphene, and are pressed and sintered through magnetic field orientation. Made by hot pressing, diffusion treatment and tempering treatment, it reduces the generation of anti-magnetization domains and improves coercive force and mechanical properties.
The magnetic and mechanical properties of rare earth permanent magnets have been improved, the use of precious rare earth metals has been reduced, and the comprehensive performance and service life of the electrodes have been improved.
Smart Images

Figure CN119132770A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of permanent magnet materials, and in particular to rare earth permanent magnets, preparation methods thereof, and motors. Background Art
[0002] Rare earth permanent magnets have the advantages of high magnetic energy product, high coercivity, relatively low price and sufficient raw material reserves, and are widely used in industry and agriculture. At present, it is difficult for rare earth permanent magnets to achieve high coercivity, high durability and bending strength at the same time without any treatment. For example, by adding precious rare earth elements to rare earth permanent magnets to improve their magnetic properties, their mechanical properties are not improved. Therefore, further research and development of rare earth permanent magnets is needed. Summary of the invention
[0003] In view of this, the present application provides a rare earth permanent magnet, a preparation method thereof, and a motor. The rare earth permanent magnet has excellent magnetic properties, good mechanical properties, and improved comprehensive performance, which helps to improve the performance of the electrode.
[0004] In a first aspect, the present application provides a rare earth permanent magnet, the rare earth permanent magnet comprising a main phase and a grain boundary phase, the main phase being dispersed in the grain boundary phase, the main phase comprising a core and a shell layer covering the core, the shell layer and the grain boundary phase comprising graphene, the core comprising RL 1 a RH 1 b Fe c Co d B e , RL 1 Contains at least one of Pr and Nd, RH 1 It includes at least one of La, Ce, Sm, Gd, Ho and Y, a, b, c, d, e are weight parts, 7.91≤a≤10.03, 18.98≤b≤20.79, 64.72≤c≤72.28, 0≤d≤2.33, 0.83≤e≤1.23, and the shell layer includes RL 2 f RL 3 g RH 2 h Fe i Co j B k M 1 l C m , RL 2 Including at least one of La, Ce, Sm, Gd, Ho and Y, RL 3 Contains at least one of Pr and Nd, RH 2including at least one of Dy and Tb, M 1 It includes at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, f, g, h, i, j, k, l, m are weight percentages, 21.64≤f+g+h≤32.64, 3.83≤g≤8.1, 6.66≤h≤8.97, 40.554≤i≤65.014, 0≤j≤2.1, 0.25≤k≤0.49, 11.5≤l≤20.58, 1.596≤m≤2.736, and the grain boundary phase includes RL 4 o RL 5 p RH 3 q Fe r Co s M 2 t C u , RL 4 Contains at least one of La, Ce and Sm, RL 5 Contains at least one of Pr and Nd, RH 3 including at least one of Dy and Tb, M 2 It includes at least one of Zr, Ga, Cu and Sn, and Al, Zn, Si and Ti, o, p, q, r, s, t, u are weight parts, and 19.39≤o+p+q≤33.857, 2.08≤p≤6.815, 9.52≤q≤14.946, 24.458≤r≤61.895, 0≤s≤1.92, 16.435≤t≤34.305, 2.28≤u≤4.56.
[0005] Optionally, in the kernel, 8≤a≤10, 19≤b≤20.5, 65.7≤c≤71, 0.5≤d≤1.8, 0.9≤e≤1.1.
[0006] Optionally, in the shell layer, 21.8≤f+g+h≤32.5, 3.9≤g≤7.8, 6.7≤h≤8.8, 42.5≤i≤63.72, 0.2≤j≤1.9, 0.28≤k≤0.45, 11.8≤l≤20.3, and 1.6≤m≤2.5.
[0007] Optionally, in the grain boundary phase, 19.5≤o+p+q≤33.5, 2.2≤p≤6.7, 9.7≤q≤14.5, 25.7≤r≤60.8, 0.2≤s≤1.7, 16.5≤t≤34, and 2.4≤u≤4.
[0008] Optionally, the ratio of the mass content of the rare earth elements in the shell to the mass content of the rare earth elements in the core is (0.744-1.093):1.
[0009] Optionally, the shell layer has a thickness of 0.1 μm-8.5 μm.
[0010] Optionally, the mass content of the grain boundary phase in the rare earth permanent magnet is 20%-40%, and the mass content of the main phase is 60%-80%.
[0011] In a second aspect, the present application provides a method for preparing a rare earth permanent magnet, comprising:
[0012] The first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material are mixed, and the raw material is pressed and sintered to obtain a rare earth permanent magnet blank, wherein the first main phase alloy raw material includes R 1 a' Fe b' Co c' B d' , R 1 The second main phase alloy raw material includes at least one of Pr and Nd, a', b', c', d' are weight parts, 25.5≤a'≤29.5, 66.4≤b'≤73.6, 0≤c'≤2, 0.9≤d'≤1.2, and the second main phase alloy raw material includes R 2 e' Fe f' Co g' B h' , R 2 The alloy comprises at least one of La, Ce, Sm, Gd, Ho and Y, wherein e', f', g' and h' are weight percentages, 27.5≤e'≤31.5, 63.85≤f'≤71.7, 0≤g'≤2.5, 0.8≤h'≤1.25, and the grain boundary phase alloy raw material comprises R 3 i' Fe j' Co k' M 3 l' , R 3 Includes at least one of La, Ce, Sm, Pr and Nd, M 3 It includes at least one of Zr, Ga, Cu, Sn, Al and Zn, i', j', k', l' are weight parts, 19≤i'≤25.2, 44.9≤j'≤71, 0≤k'≤4, 10≤l'≤25;
[0013] The grain boundary diffusion material is arranged on the surface of the rare earth permanent magnet blank, wherein the grain boundary diffusion material comprises a diffusion alloy material and modified graphene, wherein the modified graphene comprises graphene and a zinc alloy layer covering the graphene, and wherein the diffusion alloy material comprises R 4 m' R 5 n' Fe o' M 4 p' , R 4 Contains at least one of Pr and Nd, R 5 including at least one of Dy and Tb, M 4 The zinc alloy layer comprises at least one of Ga, Cu, Sn, Al and Zn, wherein m', n', o' and p' are weight percentages, 5.2≤m'≤14.5, 23.8≤n'≤31.8, 28.85≤o'≤55.5, 15.5≤p'≤24, and the zinc alloy layer comprises Zn q' Al r' Si s' Ti t' , q', r', s', t' are weight parts, 61.8≤q'≤84.87, 14.1≤r'≤34.4, 0.9≤s'≤2.2, 0.13≤t'≤0.7;
[0014] The rare earth permanent magnet is obtained after hot pressing, diffusion treatment and tempering treatment.
[0015] Optionally, before the grain boundary diffusion material is disposed on the surface of the rare earth permanent magnet blank, the method further includes: mixing the graphene with a zinc alloy material, and obtaining the modified graphene after ball milling.
[0016] Furthermore, the average particle size of the zinc alloy material is 58nm-80nm.
[0017] Furthermore, the average particle size of the modified graphene is 10nm-25nm.
[0018] Furthermore, the ball-to-material ratio in the ball mill is (5-10):1, the rotation speed is 160r / min-180r / min, and the time is 6h-10h.
[0019] Furthermore, the ball milling is performed under an inert atmosphere or vacuum conditions.
[0020] Optionally, in the diffusion alloy raw material, 6≤m'≤14, 24≤n'≤31, 30.7≤o'≤53.4, and 16≤p'≤23.
[0021] Optionally, the mass content of the modified graphene in the grain boundary diffusion material is 10%-23%.
[0022] Optionally, the mass content of the graphene in the modified graphene is 19%-38%.
[0023] Optionally, the ratio of the mass of the second main phase alloy raw material to the sum of the mass of the first main phase alloy raw material and the second main phase alloy raw material is 50%-69%.
[0024] Optionally, the ratio of the mass of the grain boundary phase alloy raw material to the sum of the mass of the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material is 5%-17%.
[0025] Optionally, the magnetic field oriented pressing molding includes processing under a magnetic field of 1.5T-3.5T and a pressure of 170MPa-210MPa for 60s-150s.
[0026] Optionally, the sintering includes treating at 1030° C.-1090° C. for 4 h-5.5 h.
[0027] Optionally, the hot pressing includes a temperature of 550°C-800°C, 80MPa-150MPa and a vacuum degree of 10 -3 Pa-10 -2 Treat under Pa conditions for 30min-150min.
[0028] Optionally, the diffusion treatment includes heating at 600°C-1000°C and vacuum degree 10 -5 Pa-10 -2 Treat under Pa conditions for 2h-12h.
[0029] Optionally, the tempering treatment includes heating at 400°C-600°C and vacuum degree 10 -5 Pa-10 -2 Treat under Pa conditions for 2.5h-10h.
[0030] Optionally, the sintering further includes a pre-tempering treatment, wherein the pre-tempering treatment includes a treatment at 890° C.-950° C. for 2.5 h-5 h, and then a treatment at 480° C.-520° C. for 3.5 h-8 h.
[0031] In a third aspect, the present application provides a motor, comprising the rare earth permanent magnet described in the first aspect or the rare earth permanent magnet produced by the preparation method described in the second aspect.
[0032] The rare earth permanent magnet provided by the present application has excellent magnetic and mechanical properties, and the rare earth permanent magnet reduces the usage of precious rare earth metals, can comprehensively utilize rare earth materials, has low preparation cost, and is conducive to its use; the electrode having the rare earth permanent magnet has excellent comprehensive performance and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic structural diagram of a rare earth permanent magnet provided in one embodiment of the present application.
[0034] Figure 2 A flow chart of a method for preparing a rare earth permanent magnet provided in one embodiment of the present application.
[0035] Figure 3 This is an electron microscope image of the rare earth permanent magnet prepared in Example 1. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] The present application provides a rare earth permanent magnet, which includes a main phase and a grain boundary phase, wherein the main phase is dispersed in the grain boundary phase, the main phase includes a core and a shell layer covering the core, the shell layer and the grain boundary phase have graphene, and the core includes RL 1 a RH 1 b Fe c Co d B e , RL 1 Contains at least one of Pr and Nd, RH 1 Including at least one of La, Ce, Sm, Gd, Ho and Y, a, b, c, d, e are weight parts, 7.91≤a≤10.03, 18.98≤b≤20.79, 64.72≤c≤72.28, 0≤d≤2.33, 0.83≤e≤1.23, the shell includes RL 2 f RL 3 g RH 2 h Fe i Co j B k M 1 l C m , RL 2 Including at least one of La, Ce, Sm, Gd, Ho and Y, RL 3 Contains at least one of Pr and Nd, RH 2 including at least one of Dy and Tb, M 1Including at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, f, g, h, i, j, k, l, m are weight percentages, 21.64≤f+g+h≤32.64, 3.83≤g≤8.1, 6.66≤h≤8.97, 40.554≤i≤65.014, 0≤j≤2.1, 0.25≤k≤0.49, 11.5≤l≤20.58, 1.596≤m≤2.736, the grain boundary phase includes RL 4 o RL 5 p RH 3 q Fe r Co s M 2 t C u , RL 4 Contains at least one of La, Ce and Sm, RL 5 Contains at least one of Pr and Nd, RH 3 including at least one of Dy and Tb, M 2 It includes at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, o, p, q, r, s, t, u are weight parts, and 19.39≤o+p+q≤33.857, 2.08≤p≤6.815, 9.52≤q≤14.946, 24.458≤r≤61.895, 0≤s≤1.92, 16.435≤t≤34.305, 2.28≤u≤4.56. Please refer to Figure 1 , is a schematic structural diagram of a rare earth permanent magnet provided in one embodiment of the present application, wherein the rare earth permanent magnet 100 includes a main phase 10 and a grain boundary phase 20, the main phase 10 is dispersed in the grain boundary phase 20, and the main phase 10 includes a core 11 and a shell 12 covering the core 11.
[0038] In the present application, the main phase is dispersed in the grain boundary phase, that is, the grain boundary phase isolates and / or covers the main phase, and the main phase is a core-shell structure, which increases the magnetocrystalline anisotropy field of the core of the main phase, reduces the magnetic exchange coupling between the grains in the core of the main phase, and inhibits the generation of reverse magnetization domains, thereby significantly enhancing the overall coercive force and high-temperature external field durability of the rare earth permanent magnet, and at the same time can guarantee the residual magnetic properties of the rare earth permanent magnet to the greatest extent; the shell layer and the grain boundary phase have graphene and the graphene is uniformly dispersed therein, which effectively improves the mechanical properties of the rare earth permanent magnet, such as bending resistance, and is conducive to improving the machinability of the rare earth permanent magnet; the shell layer of the main phase is a rare earth-rich phase with a high magnetocrystalline anisotropy field, which can effectively improve the coercive force of the rare earth permanent magnet, so that the rare earth permanent magnet has excellent magnetic properties and mechanical properties; at the same time, the rare earth permanent magnet contains a large amount of high-abundance rare earth elements (such as La, Ce, Sm, etc.), which can reduce the cost of the rare earth permanent magnet while ensuring the magnetic properties of the rare earth permanent magnet.
[0039] In this application, the kernel includes RL 1 a RH 1 b Fe c Co d B e , RL 1 Contains at least one of Pr and Nd, RH 1 Including at least one of La, Ce, Sm, Gd, Ho and Y, a, b, c, d, e are weight parts, 7.91≤a≤10.03, 18.98≤b≤20.79, 64.72≤c≤72.28, 0≤d≤2.33, 0.83≤e≤1.23. Specifically, a can be but not limited to 7.91, 8, 8.15, 8.38, 8.67, 8.93, 9.05, 9.32, 9.59, 9.81, 9.95, 10, 10.02, etc. Specifically, b can be but not limited to 19, 19.24, 19.47, 19.73, 19.91, 20, 20.5, 20.66. Specifically, c can be, but not limited to, 64.72, 65.64, 67.85, 68.18, 69.75, 70.5, 71, 72.1, etc. Specifically, d can be, but not limited to, 0, 0.5, 0.72, 0.98, 1.32, 1.59, 1.8, 1.9, 2, 2.21, etc. Specifically, e can be, but not limited to, 0.83, 0.85, 0.9, 1, 1.03, 1.1, 1.13, 1.2, etc. In one embodiment of the present application, in the kernel, 8≤a≤10, 19≤b≤20.5, 65.7≤c≤71, 0.5≤d≤1.8, 0.9≤e≤1.1, which is conducive to further improving the coercive force of the rare earth permanent magnet without affecting the residual magnetic induction intensity (remanence).
[0040] In the present application, the shell layer has graphene, and the shell layer includes RL 2 f RL 3 g RH 2 h Fe i Co j B k M 1 l C m , RL 2 Including at least one of La, Ce, Sm, Gd, Ho and Y, RL 3 Contains at least one of Pr and Nd, RH 2 including at least one of Dy and Tb, M 1 It includes at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, f, g, h, i, j, k, l, m are weight parts, 21.64≤f+g+h≤32.64, 3.83≤g≤8.1, 6.66≤h≤8.97, 40.554≤i≤65.014, 0≤j≤2.1, 0.25≤k≤0.49, 11.5≤l≤20.58, 1.596≤m≤2.736. It can be understood that M 1Including Al, Zn, Si and Ti, and also including at least one of Zr, Ga, Cu and Sn. Specifically, f+g+h can be, but not limited to, 21.64, 21.8, 23.7, 25.5, 27.24, 28.37, 30.26, 32.5, etc. Specifically, g can be, but not limited to, 3.83, 3.9, 3.95, 4, 4.25, 5.72, 6.94, 7, 7.34, 7.8, 8, etc. Specifically, h can be, but not limited to, 6.7, 6.9, 7, 7.2, 7.6, 7.9, 8, 8.2, 8.5, 8.8, 8.9, etc. Specifically, i can be, but not limited to, 40.554, 42.5, 43.2, 47.8, 50.5, 55.7, 58.1, 60.4, 63.3, 63.72, 65, etc. Specifically, j can be, but not limited to, 0, 0.2, 0.7, 1, 1.3, 1.5, 1.7, 1.9, 2, 2.1, etc. Specifically, k can be, but not limited to, 0.28, 0.3, 0.34, 0.37, 0.4, 0.45, 0.47, etc. Specifically, l can be, but not limited to, 11.8, 12.5, 14, 15.6, 17.3, 18.9, 20, 20.3, 20.5, etc. Specifically, m can be, but not limited to, 1.6, 1.841, 1.95, 2, 2.245, 2.5, 2.67, etc. In one embodiment of the present application, in the shell layer, 21.8≤f+g+h≤32.5, 3.9≤g≤7.8, 6.7≤h≤8.8, 42.5≤i≤63.72, 0.2≤j≤1.9, 0.28≤k≤0.45, 11.8≤l≤20.3, 1.6≤m≤2.5, which is beneficial to further improve the coercive force and mechanical properties of the rare earth permanent magnet without affecting the residual magnetism.
[0041] In one embodiment of the present application, the shell layer includes 0.061 parts to 0.098 parts of Si by weight. Specifically, by weight, the shell layer may include, but is not limited to, 0.065 parts, 0.07 parts, 0.083 parts, 0.09 parts, or 0.095 parts of Si. In one embodiment, by weight, the shell layer may include 0.07 parts to 0.09 parts of Si to further improve the performance of the rare earth permanent magnet.
[0042] In one embodiment of the present application, the shell layer includes 0.0091 parts to 0.0312 parts of Ti by weight. Specifically, by weight, the shell layer may include, but is not limited to, 0.01 parts, 0.015 parts, 0.02 parts, 0.027 parts, 0.03 parts, or 0.031 parts of Ti. In one embodiment, by weight, the shell layer may include 0.01 parts to 0.03 parts of Ti to further improve the performance of the rare earth permanent magnet.
[0043] In one embodiment of the present application, the shell contains Dy2Fe 14 B phase and Tb2Fe 14 At least one of the B phases, Pr2Fe 14 B phase and Nd2Fe 14 At least one of the B phases can further increase the crystal magnetic anisotropy constant of the main phase surface and reduce the decrease in magnetic properties caused by high-abundance rare earth elements (such as Ce).
[0044] In one embodiment of the present application, the ratio of the mass content of the rare earth elements in the shell to the mass content of the rare earth elements in the core is (0.744-1.093):1, which is conducive to further improving the magnetic properties of the rare earth permanent magnet. Specifically, the ratio of the mass content of the rare earth elements in the shell to the mass content of the rare earth elements in the core can be, but not limited to, 0.75:1, 0.8:1, 0.807:1, 0.83:1, 0.85:1, 0.885:1, 0.9:1, 0.93:1, 0.97:1, 1:1, 1.083:1, 1.09:1, etc. In one embodiment, the ratio of the mass content of the rare earth elements in the shell to the mass content of the rare earth elements in the core can be (0.807-1.083):1. In another embodiment, the ratio of the mass content of the rare earth elements in the shell to the mass content of the rare earth elements in the core can be (0.85-1):1. In yet another embodiment, the ratio of the mass content of the rare earth elements in the shell layer to the mass content of the rare earth elements in the core layer may be (0.862-0.991):1.
[0045] In one embodiment of the present application, the thickness of the shell layer is 0.1 μm-8.5 μm, which can increase the magnetocrystalline anisotropy field of the main phase, reduce the magnetic exchange coupling between the main phases, and increase the coercive force of the permanent magnet. Specifically, the thickness of the shell layer can be, but is not limited to, 0.2 μm, 0.5 μm, 1 μm, 1.7 μm, 2.5 μm, 4 μm, 5 μm, 6 μm, 7.4 μm, 8 μm, etc. In one embodiment, the thickness of the shell layer can be 1 μm-7.4 μm. In another embodiment, the thickness of the shell layer can be 1.2 μm-7 μm. In yet another embodiment, the thickness of the shell layer can be 1.8 μm-6 μm.
[0046] In the present application, the shell layer may partially or completely cover the core. In one embodiment of the present application, the coverage of the shell layer is greater than or equal to 60%. Specifically, the coverage of the shell layer may be, but is not limited to, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. The coverage of the shell layer is the percentage of the surface area of the core covered by the shell layer to the total surface area of the core. In one embodiment, the shell layer completely covers the core, that is, the coverage of the shell layer is 100%, which can further improve the magnetic properties of the rare earth permanent magnet. In another embodiment, cores accounting for more than 90% of the total number of cores are completely covered by the shell layer.
[0047] In the present application, the grain boundary phase has graphene, and the grain boundary phase includes RL 4 o RL 5 p RH 3 q Fe r Co s M 2 t C u , RL 4 Contains at least one of La, Ce and Sm, RL 5 Contains at least one of Pr and Nd, RH 3 including at least one of Dy and Tb, M 2 It includes at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, o, p, q, r, s, t, u are weight parts, and 19.39≤o+p+q≤33.857, 2.08≤p≤6.815, 9.52≤q≤14.946, 24.458≤r≤61.895, 0≤s≤1.92, 16.435≤t≤34.305, 2.28≤u≤4.56. It can be understood that M 2Including Al, Zn, Si and Ti, and also including at least one of Zr, Ga, Cu and Sn. Specifically, o+p+q can be but not limited to 19.5, 20, 20.7, 22.9, 25, 27.3, 29.5, 30, 33.5, 33.8, etc. Specifically, p can be but not limited to 2.2, 2.7, 3, 3.5, 4, 4.8, 5, 5.2, 6, 6.7, 6.8, etc. Specifically, q can be but not limited to 9.7, 10, 10.3, 11.5, 12, 12.7, 13, 14.5, 14.8, etc. Specifically, r can be but not limited to 25, 25.7, 27.5, 30, 38.1, 47, 50, 55, 60.8, 61, etc. Specifically, s can be, but not limited to, 0, 0.2, 0.5, 0.8, 1, 1.3, 1.5, 1.7, 1.8, etc. Specifically, t can be, but not limited to, 16.5, 18, 20, 23.8, 28.1, 30.5, 34, etc. Specifically, u can be, but not limited to, 2.3, 2.4, 3.1, 3.7, 4, 4.3, etc. In one embodiment of the present application, in the grain boundary phase, 19.5≤o+p+q≤33.5, 2.2≤p≤6.7, 9.7≤q≤14.5, 25.7≤r≤60.8, 0.2≤s≤1.7, 16.5≤t≤34, 2.4≤u≤4, which is conducive to further improving the coercive force and mechanical properties of the rare earth permanent magnet without affecting the remanence.
[0048] In one embodiment of the present application, the grain boundary phase includes 0.087 parts to 0.164 parts of Si by weight. Specifically, by weight, the grain boundary phase may include, but is not limited to, 0.09 parts, 0.1 parts, 0.13 parts, 0.15 parts, or 0.16 parts of Si. In one embodiment, by weight, the grain boundary phase may include 0.09 parts to 0.15 parts of Si, further improving the performance of the rare earth permanent magnet.
[0049] In one embodiment of the present application, the grain boundary phase includes 0.0091 parts to 0.0312 parts of Ti by weight. Specifically, by weight, the grain boundary phase may include, but is not limited to, 0.02 parts, 0.03 parts, 0.035 parts, 0.04 parts, or 0.05 parts of Ti. In one embodiment, by weight, the grain boundary phase may include 0.02 parts to 0.05 parts of Ti, further improving the performance of the rare earth permanent magnet.
[0050] In one embodiment of the present application, the mass content of the grain boundary phase in the rare earth permanent magnet is 20%-40%, and the mass content of the main phase is 60%-80%, which further improves the magnetic properties and mechanical properties of the rare earth permanent magnet. Specifically, the mass content of the grain boundary phase in the rare earth permanent magnet can be but not limited to 20%, 22%, 25%, 28%, 30%, 33%, 35%, 37%, 40%, etc.; the mass content of the main phase in the rare earth permanent magnet can be but not limited to 60%, 63%, 65%, 67%, 70%, 72%, 75%, 78%, 80%, etc. In one embodiment, the mass content of the grain boundary phase in the rare earth permanent magnet is 22%-37%, and the mass content of the main phase is 63%-78%. In another embodiment, the mass content of the grain boundary phase in the rare earth permanent magnet is 25%-35%, and the mass content of the main phase is 65%-75%.
[0051] In the present application, the Co element in the rare earth permanent magnet can increase its Curie temperature, reduce the coercive force temperature coefficient, and improve the temperature stability of the permanent magnet.
[0052] In the present application, at least one of the core, shell and grain boundary phase of the rare earth permanent magnet may contain trace amounts of impurity elements. These impurity elements may be brought by metal raw materials, and specifically, the impurity elements may include but are not limited to at least one of Ca, Ni, Mn, Mg, Cr, Er, W, Mo, Ca, N, O, S and P.
[0053] In one embodiment of the present application, the thickness of the rare earth permanent magnet is 1mm-10mm, which is conducive to the performance of the magnetic properties and mechanical properties of the rare earth permanent magnet. Specifically, the thickness of the rare earth permanent magnet can be but is not limited to 1mm, 3mm, 5mm, 6mm, 7mm, 10mm, etc. In one embodiment, the thickness of the rare earth permanent magnet can be 2mm-7mm. In one embodiment of the present application, the rare earth permanent magnet can be a sheet structure, which is conducive to the performance of the magnetic properties and mechanical properties of the rare earth permanent magnet.
[0054] In one embodiment of the present application, the remanence of the rare earth permanent magnet is greater than or equal to 12.56 kGs, the intrinsic coercive force is greater than or equal to 24.63 kOe, the irreversible loss of magnetic flux at 7 kOe and 180 ° C for 10 hours is less than or equal to 10.96%, and the bending strength is greater than or equal to 295 MPa. The rare earth permanent magnet has excellent magnetic and mechanical properties, which is conducive to the use of rare earth permanent magnets. In one embodiment of the present application, the remanence of the rare earth permanent magnet can be 12.92 Gs-13.03 kGs, the intrinsic coercive force can be 28.23 kOe-29.74 kOe, the irreversible loss of magnetic flux at 7 kOe and 180 ° C for 10 hours can be 5.44%-6.8%, and the bending strength can be 364-394 MPa. In one embodiment of the present application, the remanence of the rare earth permanent magnet can be 12.92Gs-13.03kGs, the intrinsic coercive force can be 29.32kOe-29.74kOe, the irreversible loss of magnetic flux at 7kOe and 180°C for 10 hours can be 5.44%-6%, and the bending strength can be 370MPa-394MPa.
[0055] The present application also provides a permanent magnet, comprising a rare earth permanent magnet in any of the above embodiments and a grain boundary diffusion layer arranged on at least one surface of the rare earth permanent magnet. In one embodiment of the present application, the thickness of the grain boundary diffusion layer can be 5μm-15μm, which can avoid affecting the magnetic properties of the rare earth permanent magnet. Specifically, the thickness of the grain boundary diffusion layer can be but is not limited to 5μm, 7μm, 10μm, 12μm, 14μm, 15μm, etc. In the present application, the grain boundary diffusion layer on the surface of the rare earth permanent magnet can be removed and then the grain boundary diffusion layer can be recovered to achieve the reuse of the grain boundary diffusion layer material.
[0056] The present application also provides a method for preparing a rare earth permanent magnet, comprising mixing a first main phase alloy raw material, a second main phase alloy raw material and a grain boundary phase alloy raw material, and obtaining a rare earth permanent magnet blank after magnetic field orientation pressing and sintering, wherein the first main phase alloy raw material comprises R 1 a' Fe b' Co c' B d' , R 1 The second main phase alloy raw material includes R 2 e' Fe f' Co g' B h' , R 2It includes at least one of La, Ce, Sm, Gd, Ho and Y, e', f', g', h' are weight parts, 27.5≤e'≤31.5, 63.85≤f'≤71.7, 0≤g'≤2.5, 0.8≤h'≤1.25, and the grain boundary phase alloy raw materials include R 3 i' Fe j' Co k' M 3 l' , R 3 Includes at least one of La, Ce, Sm, Pr and Nd, M 3 The invention comprises at least one of Zr, Ga, Cu, Sn, Al and Zn, i', j', k' and l' are weight percentages, 19≤i'≤25.2, 44.9≤j'≤71, 0≤k'≤4 and 10≤l'≤25; a grain boundary diffusion material is arranged on the surface of a rare earth permanent magnet blank, the grain boundary diffusion material comprises a diffusion alloy material and modified graphene, the modified graphene comprises graphene and a zinc alloy layer covering the graphene, the diffusion alloy material comprises R 4 m' R 5 n' Fe o' M 4 p' , R 4 Contains at least one of Pr and Nd, R 5 including at least one of Dy and Tb, M 4 The zinc alloy layer includes at least one of Ga, Cu, Sn, Al and Zn, wherein m', n', o' and p' are weight percentages, 5.2≤m'≤14.5, 23.8≤n'≤31.8, 28.85≤o'≤55.5, 15.5≤p'≤24, and the zinc alloy layer includes Zn q' Al r' Si s' Ti t' , q', r', s', t' are weight parts, 61.8≤q'≤84.87, 14.1≤r'≤34.4, 0.9≤s'≤2.2, 0.13≤t'≤0.7; the rare earth permanent magnet is obtained after hot pressing, diffusion treatment and tempering treatment.
[0057] See also Figure 2 , is a flow chart of a method for preparing a rare earth permanent magnet provided in one embodiment of the present application, comprising:
[0058] S101: mixing the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material, pressing and molding through magnetic field orientation, and sintering to obtain a rare earth permanent magnet blank.
[0059] S102: disposing a grain boundary diffusion material on the surface of the rare earth permanent magnet blank, wherein the grain boundary diffusion material includes a diffusion alloy material and modified graphene, and the modified graphene includes graphene and a zinc alloy layer covering the graphene.
[0060] S103: A rare earth permanent magnet is obtained after hot pressing, diffusion treatment and tempering treatment.
[0061] The first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material used in the preparation method of the rare earth permanent magnet provided by the present application contain a large amount of high-abundance rare earth elements (such as La, Ce, Sm, etc.), which reduces the cost of the rare earth permanent magnet; at the same time, the diffusion alloy material and the graphene in the grain boundary diffusion material have different properties, and the interface wettability of the graphene is poor. The graphene is modified by the zinc alloy material so that the modified graphene has a suitable density and wettability, and the interface bonding force between the modified graphene and the diffusion alloy material can be increased during the hot pressing process, and the diffusion kinetic energy of the molten diffusion alloy material can be increased, so that the graphene diffuses into the interior of the rare earth permanent magnet blank along with the diffusion alloy material and is uniformly distributed in the grain boundary together, so as to better play the role of grain boundary modification; the modified graphene and the diffusion alloy material enter the grain boundary, wherein R 5 or R 4 It undergoes a substitution reaction with at least one of Pr and Nd or at least one of La and Ce in the alloy raw materials to generate Dy2Fe on the surface of the main phase. 14 B and Tb2Fe 14 At least one of B, Pr2Fe 14 B and Nd2Fe 14 At least one of B, that is, a shell layer is generated, a main phase of a core-shell structure is obtained, the crystalline magnetic anisotropy constant of the main phase surface is increased, and the generated rare earth element-enriched shell layer can reduce or eliminate the defect of easy demagnetization of the magnet grain boundary phase, inhibit the generation of reverse magnetization domains, and make up for the MM2Fe 14 The decrease in magnetic properties brought about by B effectively improves the coercive force of the entire magnet, while having little effect on the residual magnetism; therefore, the preparation method provided in the present application can improve the coercive force, high-temperature external field durability and mechanical properties of the rare earth permanent magnet without affecting the residual magnetic properties, thereby obtaining a rare earth permanent magnet with excellent comprehensive performance.
[0062] In S101, a rare earth permanent magnet blank is produced by mixing a first main phase alloy raw material, a second main phase alloy raw material and a grain boundary phase alloy raw material, pressing and molding them in a magnetic field orientation, and sintering them.
[0063] In the present application, the first main phase alloy raw material includes R 1 a' Fe b' Co c' B d' , R1 Including at least one of Pr and Nd, a', b', c', d' are weight parts, 25.5≤a'≤29.5, 66.4≤b'≤73.6, 0≤c'≤2, 0.9≤d'≤1.2. Specifically, a' can be but not limited to 25.5, 26, 26.5, 27, 27.5, 28, 28.5, 29, etc. Specifically, b' can be but not limited to 66.5, 67, 68, 69, 70, 72, 73, etc. Specifically, c' can be but not limited to 0, 0.5, 1, 1.5, 2, etc. Specifically, d' can be but not limited to 1, 1.05, 1.1, 1.15, 1.2, etc.
[0064] In the present application, the second main phase alloy raw material includes R 2 e' Fe f' Co g' B h' , R 2 Including at least one of La, Ce, Sm, Gd, Ho and Y, e', f', g', h' are weight parts, 27.5≤e'≤31.5, 63.85≤f'≤71.7, 0≤g'≤2.5, 0.8≤h'≤1.25. Specifically, e' can be but not limited to 27.8, 28, 28.5, 29, 29.2, 30, 31, etc. Specifically, f' can be but not limited to 63.85, 65.5, 67.2, 68.9, 69, 70, 71, etc. Specifically, g' can be but not limited to 0, 0.5, 1, 1.5, 2, etc. Specifically, h' can be but not limited to 0.9, 1, 1.1, 1.2, etc.
[0065] In the present application, the grain boundary phase alloy raw materials include R 3 i' Fe j' Co k' M 3 l' , R 3 Includes at least one of La, Ce, Sm, Pr and Nd, M 3 Including at least one of Zr, Ga, Cu, Sn, Al and Zn, i', j', k', l' are weight parts, 19≤i'≤25.2, 44.9≤j'≤71, 0≤k'≤4, 10≤l'≤25. Specifically, i' can be but not limited to 20, 21, 22, 23, 24, 25, etc. Specifically, j' can be but not limited to 45, 50.2, 53.6, 57.8, 61.3, 65.9, 69.6, 70, etc. Specifically, l' can be but not limited to 12, 15, 17, 20, 23, 24, etc.
[0066] In one embodiment of the present application, mixing the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material includes separately smelting the first main phase alloy raw material, the second main phase alloy raw material, and the grain boundary phase alloy raw material to obtain the first main phase alloy raw material ingot or quick-solidified thin sheet, the second main phase alloy raw material ingot or quick-solidified thin sheet, and the grain boundary phase alloy raw material ingot or quick-solidified thin sheet; mixing the first main phase alloy raw material ingot or quick-solidified thin sheet, the second main phase alloy raw material ingot or quick-solidified thin sheet, and the grain boundary phase alloy raw material ingot or quick-solidified thin sheet. In another embodiment of the present application, mixing the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material includes separately smelting the first main phase alloy raw material, the second main phase alloy raw material, and the grain boundary phase alloy raw material to obtain the first main phase alloy raw material ingot or quick-solidified sheet, the second main phase alloy raw material ingot or quick-solidified sheet, and the grain boundary phase alloy raw material ingot or quick-solidified sheet; mixing the first main phase alloy raw material ingot or quick-solidified sheet, the second main phase alloy raw material ingot or quick-solidified sheet, and the grain boundary phase alloy raw material ingot or quick-solidified sheet, and then crushing and powdering. In another embodiment of the present application, mixing the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material includes separately smelting the first main phase alloy raw material, the second main phase alloy raw material, and the grain boundary phase alloy raw material to obtain the first main phase alloy raw material ingot or quick-solidified sheet, the second main phase alloy raw material ingot or quick-solidified sheet, and the grain boundary phase alloy raw material ingot or quick-solidified sheet; crushing and powdering the first main phase alloy raw material ingot or quick-solidified sheet, the second main phase alloy raw material ingot or quick-solidified sheet, and the grain boundary phase alloy raw material ingot or quick-solidified sheet to obtain the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material, and then mixing the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material.
[0067] In the present application, the method well known to those skilled in the art can be used for smelting to obtain a quick-setting thin sheet. In one embodiment, a quick-setting belt-spinning process can be used to make a quick-setting thin strip, and the belt-spinning speed (for example, the surface linear speed of the copper rod) can be 1m / s-2.5m / s (such as 1m / s, 1.2m / s, 1.5m / s, 1.9m / s, 2m / s, 2.3m / s, etc.). In the present application, the method well known to those skilled in the art can be used for crushing, as long as the obtained ingot or belt-spinning can be fully crushed to obtain crushed powder. Specifically, the hydrogen crushing method can be used. In one embodiment, the process of hydrogen crushing includes absorbing hydrogen for 1h-3h (such as 1h, 1.5h, 2h, 2.5h, 2.8h, etc.) at 15°C-25°C (such as 17°C, 18°C, 20°C, 23°C, 24°C, etc.) under a hydrogen pressure of 0.1MPa-1.5MPa (such as 0.2MPa, 0.5MPa, 0.8MPa, 1MPa, 1.3MPa, etc.), and dehydrogenating for 4h-8h (such as 4.5h, 5h, 6h, 7h, 8h, etc.) at 500°C-650°C (such as 525°C, 550°C, 570°C, 600°C, 630°C, etc.). In the present application, the method well known to those skilled in the art can be used for powdering, as long as the hydrogen crushing powder can be made into alloy powder of the target particle size. The method of airflow milling can be used, and an antioxidant needs to be added before airflow milling. Specifically, the antioxidant may include, but is not limited to, a special antioxidant for NdFeB, for example, a special antioxidant for NdFeB purchased from Beijing Juncefeng Technology Development Co., Ltd., with a brand name of KM-01. In one embodiment, by weight, the hydrogen powder is 100 parts, and the antioxidant is 0.03-0.15 parts (such as 0.05 parts, 0.08 parts, 0.1 parts, 0.13 parts, etc.). In one embodiment, an alloy powder with an average particle size of 2μm-4.5μm (such as 2.5μm, 3μm, 3.2μm, 3.5μm, 3.7μm, 4μm, etc.) can be obtained by powdering. In the present application, the alloy powder can be mixed with a lubricant to improve the dispersibility of the alloy powder. For example, the alloy powder of the first main phase alloy raw material, the alloy powder of the second main phase alloy raw material, and the alloy powder of the grain boundary phase alloy raw material can be mixed with the lubricant respectively, and then all mixed; or the alloy powder of the first main phase alloy raw material, the alloy powder of the second main phase alloy raw material, and the alloy powder of the grain boundary phase alloy raw material can be mixed and then mixed with the lubricant. In one embodiment, by weight, the alloy powder is 100 parts, and the lubricant is 0.02 parts to 0.2 parts (such as 0.05 parts, 0.08 parts, 0.1 parts, 0.13 parts, 0.15 parts, 0.19 parts, etc.). Specifically, the lubricant can include but is not limited to at least one of gasoline, oleic acid, stearic acid, polyethylene glycol, dehydrated sorbitan and stearic acid glyceryl ester.
[0068] In one embodiment of the present application, the ratio of the mass of the second main phase alloy raw material to the sum of the mass of the first main phase alloy raw material and the second main phase alloy raw material is 50%-69%. It can be understood that the mass of the first main phase alloy raw material is m1, the mass of the first main phase alloy raw material is m2, and m2 / (m1+m2) is 50%-69%, which is conducive to obtaining a rare earth permanent magnet with excellent comprehensive performance. Specifically, the ratio of the mass of the second main phase alloy raw material to the sum of the mass of the first main phase alloy raw material and the second main phase alloy raw material can be, but is not limited to, 50%, 53%, 55%, 57%, 60%, 63%, 65%, 68%, etc.
[0069] In one embodiment of the present application, the ratio of the mass of the grain boundary phase alloy raw material to the sum of the mass of the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material is 5%-17%. It can be understood that the mass of the first main phase alloy raw material is m1, the mass of the first main phase alloy raw material is m2, the mass of the grain boundary phase alloy raw material is m3, and m3 / (m1+m2+m3) is 5%-17%, which is conducive to obtaining a rare earth permanent magnet with excellent comprehensive performance. Specifically, the ratio of the mass of the grain boundary phase alloy raw material to the sum of the mass of the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material can be, but not limited to, 5%, 7%, 10%, 13%, 15%, 17%, etc.
[0070] In one embodiment of the present application, magnetic field oriented pressing includes processing for 60s-150s (such as 60s, 80s, 100s, 115s, 130s, 145s, etc.) under a magnetic field of 1.5T-3.5T (such as 1.5T, 2T, 2.3T, 2.5T, 2.8T, 3T, 3.3T, etc.) and a pressure of 170MPa-210MPa (such as 170MPa, 180MPa, 190MPa, 200MPa, 210MPa, etc.), which is beneficial to the forming of the rare earth permanent magnet blank and ensure the magnetic properties of the obtained rare earth permanent magnet.
[0071] In one embodiment of the present application, sintering includes treating at 1030° C.-1090° C. for 4 h-5.5 h. Specifically, the sintering temperature may be, but is not limited to, 1030° C., 1040° C., 1050° C., 1060° C., 1070° C., 1080° C., etc., and the sintering time may be, but is not limited to, 4 h, 4.5 h, 5 h, 5.5 h, etc.
[0072] In one embodiment of the present application, a pre-tempering treatment is also included after sintering. The performance of the rare earth permanent magnet is improved by pre-tempering. In one embodiment of the present application, the pre-tempering treatment includes treating at 890°C-950°C (such as 900°C, 910°C, 920°C, 930°C, 940°C, etc.) for 2.5h-5h (such as 3h, 3.5h, 4h, 4.5h, etc.), and then treating at 480°C-520°C (such as 490°C, 500°C, 510°C, 515°C, etc.) for 3.5h-8h (such as 4h, 4.5h, 5h, 6h, 7h, 8h, etc.), which is conducive to the flow and distribution of the neodymium-rich phase between the main phases, thereby helping to improve the performance of the rare earth permanent magnet. In the present application, the rare earth permanent magnet blank can also be machined to obtain a structure of the desired shape and size.
[0073] In one embodiment of the present application, the thickness of the rare earth permanent magnet blank can be 1mm-10mm, which is conducive to the diffusion of subsequent grain boundary diffusion materials. Specifically, the thickness of the rare earth permanent magnet blank can be but not limited to 1mm, 2mm, 5mm, 7mm, 8mm, etc. In one embodiment, the thickness of the rare earth permanent magnet blank can be 2mm-7mm. In one embodiment of the present application, the rare earth permanent magnet blank can be a sheet structure, which is conducive to the diffusion of subsequent grain boundary diffusion materials.
[0074] In S102, the grain boundary diffusion material includes a diffusion alloy material, and the diffusion alloy material includes R 4 m' R 5 n' Fe o' M 4 p' , R 4 Contains at least one of Pr and Nd, R 5 including at least one of Dy and Tb, M 4Including at least one of Ga, Cu, Sn, Al and Zn, m', n', o', p' are weight parts, 5.2≤m'≤14.5, 23.8≤n'≤31.8, 28.85≤o'≤55.5, 15.5≤p'≤24. Specifically, m' can be but not limited to 5.5, 6, 6.8, 7.4, 8.5, 9, 10.7, 12, 13, 14, etc. Specifically, n' can be but not limited to 24, 25.7, 28.1, 29.5, 30, 31, etc. Specifically, o' can be but not limited to 29, 30.7, 32.5, 35.7, 40.1, 45.4, 48.5, 50, 53.4, 53.7, etc. Specifically, p' can be, but is not limited to, 16, 17.5, 19, 20.3, 21.5, 23, etc. In one embodiment of the present application, in the diffusion alloy raw material, 6≤m'≤14, 24≤n'≤31, 30.7≤o'≤53.4, 16≤p'≤23, which is further conducive to obtaining a rare earth permanent magnet with high coercivity and good mechanical properties at low cost and with little effect on residual magnetism. The grain boundary diffusion material also includes modified graphene, the modified graphene includes graphene and a zinc alloy layer covering the graphene, the zinc alloy layer includes Zn q' Al r' Si s' Ti t' , q', r', s', t' are weight parts, 61.8≤q'≤84.87, 14.1≤r'≤34.4, 0.9≤s'≤2.2, 0.13≤t'≤0.7. Specifically, q' can be, but not limited to, 62, 65, 68, 70.5, 74.8, 78.1, 80.5, 82.7, etc. Specifically, r' can be, but not limited to, 15, 18.5, 20.7, 22.3, 25.5, 29.1, 30.5, 33.6, etc. Specifically, s' can be, but not limited to, 1, 1.2, 1.5, 1.8, 2, 2.1, etc. Specifically, t' can be, but not limited to, 0.2, 0.35, 0.5, 0.62, 0.7, etc.
[0075] In the related art, structural defects are prone to occur at the junction of the main phase and the grain boundary of the rare earth permanent magnet. The area of the structural defects is the nucleation center of the reverse magnetization domain, and the reverse magnetization domain is prone to cause demagnetization of the magnet. The grain boundary phase alloy raw material provided by the present application has a low-melting-point metal element, which can reduce the melting point of the grain boundary phase, so that the grain boundary phase alloy raw material melts during the subsequent diffusion process and becomes a diffusion channel for the grain boundary diffusion material. The grain boundary diffusion material diffuses along the low-melting-point grain boundary phase, reducing or eliminating the defect of easy demagnetization of the impurity phase of the magnet grain boundary, and inhibiting the generation of reverse magnetization domains.
[0076] In one embodiment of the present application, the grain boundary diffusion material is arranged on the surface of the rare earth permanent magnet blank, and it also includes: mixing graphene with a zinc alloy material, and obtaining modified graphene after ball milling. Graphene is a tightly packed hexagonal honeycomb two-dimensional atomic crystal structure formed by sp2 orbital hybridization of carbon atoms. It has ultra-high Young's modulus and tensile strength, so it is an ideal reinforcement phase and can improve the mechanical properties of rare earth permanent magnets. When graphene is directly used as a grain boundary diffusion material, it is difficult for graphene to diffuse into the interior of the rare earth permanent magnet, and even if it enters, it is difficult to disperse evenly, and the improvement of its mechanical properties is limited. It can be understood that the zinc alloy material is Zn q' Al r' Si s' Ti t' The zinc alloy material in the present application belongs to a low melting point alloy system, has good casting performance, and has no effect on the magnetic properties of the rare earth permanent magnet. The zinc alloy material is coated with graphene to form modified graphene, which increases the overall density of the graphene and improves the interface wettability between the graphene and the diffusion alloy material, so that the graphene can fully contact the diffusion alloy material, and the interface bonding between the graphene and the diffusion alloy material is improved. The graphene can diffuse into the interior of the rare earth permanent magnet blank along with the diffusion alloy material and be evenly distributed in the grain boundaries, thereby significantly improving the mechanical properties of the rare earth permanent magnet.
[0077] In one embodiment of the present application, the ball-to-material ratio in ball milling is (5-10):1, the rotation speed is 160r / min-180r / min, and the time is 6h-10h, which is beneficial to the coating of graphene by zinc alloy, improves the coating uniformity and coating efficiency, and does not damage the material structure, so that graphene can play an effective role, and in the process of ball milling, due to the good ductility of the zinc alloy material, it can be sheet-shaped, as an inclusion to increase the specific surface area that can accommodate graphene, so that the graphene sheet is embedded in the surface of the zinc alloy material, thereby achieving a firm combination. Specifically, the ball-to-material ratio in ball milling can be but not limited to 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., the rotation speed can be but not limited to 160r / min, 165r / min, 170r / min, 175r / min, 180r / min, etc., and the time can be but not limited to 6h, 7h, 8h, 9h, 10h, etc. In one embodiment of the present application, ball milling can be performed in an inert atmosphere (such as argon, etc.) or under vacuum conditions.
[0078] In one embodiment of the present application, the zinc alloy material can be prepared by a rapid solidification atomization method. In one embodiment, the ingredients are mixed according to the ratio of each element in the zinc alloy material and then heated to 485°C-518°C for smelting. The smelting process uses an inert gas (such as argon, etc.) as a protective atmosphere. The cooling rate of the gas atomization method is 103K / s-105K / s, and the atomization pressure is 20MPa-50MPa. Among them, the atomizing medium can be argon. The above method can produce a zinc alloy material with a smaller particle size, a lower melting point, a uniform composition, a fast melting speed, and good wettability.
[0079] In one embodiment of the present application, the average particle size of the zinc alloy material is 58nm-80nm, which is conducive to the coating of graphene. Specifically, the average particle size of the zinc alloy material can be, but is not limited to, 60nm, 65nm, 68nm, 70nm, 73nm, 75nm, 79nm, etc. In one embodiment, the average particle size of the zinc alloy material can be 60nm-78nm.
[0080] In one embodiment of the present application, the melting point of the zinc alloy material is less than or equal to 650° C. That is, the melting point of the zinc alloy layer is less than or equal to 650° C., and a molten state is formed during the diffusion process, which promotes the diffusion of graphene, is beneficial to further improve the mechanical properties of the rare earth permanent magnet, and does not affect the magnetic properties of the rare earth permanent magnet.
[0081] In one embodiment of the present application, the average particle size of graphene is 6nm-23nm, which is conducive to the coating of zinc alloy materials. Specifically, the average particle size of graphene can be but is not limited to 6nm, 10nm, 13nm, 15nm, 17nm, 20nm or 23nm. In one embodiment, the average particle size of graphene is 10nm-20nm.
[0082] In one embodiment of the present application, the average particle size of the modified graphene is 10nm-25nm, which is conducive to further improving the mechanical properties of the rare earth permanent magnet, improving its uniform dispersion in the rare earth permanent magnet, and reducing the preparation cost and process difficulty. Specifically, the average particle size of the modified graphene can be but is not limited to 10nm, 12nm, 15nm, 18nm, 20nm, 23nm, etc. In one embodiment, the average particle size of the modified graphene can be 15nm-23nm.
[0083] In one embodiment of the present application, the mass content of graphene in the modified graphene is 19%-38%, which is further beneficial to improve the mechanical properties of the rare earth permanent magnet. Specifically, the mass content of graphene in the modified graphene can be, but is not limited to, 20%, 23%, 25%, 27%, 30%, 33%, 35% or 37%, etc.
[0084] In one embodiment of the present application, the mass content of modified graphene in the grain boundary diffusion material is 10%-23%. Specifically, the mass content of modified graphene in the grain boundary diffusion material can be, but is not limited to, 10%, 13%, 15%, 18%, 20%, 22%, etc. In one embodiment, the mass content of modified graphene in the grain boundary diffusion material is 12%-22%.
[0085] In one embodiment of the present application, the diffusion alloy material can be prepared by a melt quenching method. In one embodiment, the quenching speed can be 18m / s-28m / s. In another embodiment, the quenching speed can be 19m / s-26m / s. In a specific embodiment, the diffusion alloy material is prepared according to the proportion of each element in the diffusion alloy material, mixed and then smelted, and a thin strip of the diffusion alloy material is prepared at a quenching speed of 18m / s-28m / s.
[0086] In one embodiment of the present application, the average particle size of the diffusion alloy material is 30nm-85nm, which is conducive to uniform mixing and dispersion with the modified graphene, and at the same time, the melt adhesion bonding effect with the rare earth permanent magnet blank is good, the preparation difficulty is small, and the preparation cost is low. Specifically, the average particle size of the diffusion alloy material can be, but is not limited to, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 75nm, 80nm, etc. In one embodiment, the average particle size of the diffusion alloy material can be 35nm-80nm.
[0087] In one embodiment of the present application, the melting point of the diffusion alloy material is less than or equal to 650°C, and a molten state is formed during the diffusion process, which promotes the diffusion of graphene, is beneficial to further improve the mechanical properties of the rare earth permanent magnet, and does not affect the magnetic properties of the rare earth permanent magnet. In one embodiment, the melting point of the diffusion alloy material can be 450°C-650°C.
[0088] In the present application, the rare earth permanent magnet blank has a first surface and a second surface that are arranged oppositely, and the grain boundary diffusion material can be arranged on the first surface, or on the second surface, or on both the first surface and the second surface, and a rare earth permanent magnet with excellent comprehensive performance can be obtained. The present application does not limit the mixing method of the diffusion alloy material and the modified graphene, for example, mechanical stirring, ball milling, etc. can be used; there is no limit to the form in which the grain boundary diffusion material is coated on the surface of the rare earth permanent magnet blank, such as coating, spraying, coating, impregnation, suspension adhesion, roller electrophoresis, etc. In one embodiment, the grain boundary diffusion material can be directly coated on the first surface and the second surface of the rare earth permanent magnet blank, which is simple to operate and can reduce the preparation cost.
[0089] In one embodiment of the present application, the rare earth permanent magnet blank may be subjected to surface treatment before the grain boundary diffusion material is provided. Specifically, the surface treatment may be, but is not limited to, pickling or mechanical polishing. In one embodiment, pickling may be performed using a 0.3wt% nitric acid solution.
[0090] In S103, a rare earth permanent magnet with excellent magnetic properties and good mechanical properties is obtained after hot pressing and diffusion treatment.
[0091] In one embodiment of the present application, hot pressing includes heating at 550°C-800°C (such as 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.), 80MPa-150MPa (such as 80MPa, 85MPa, 90MPa, 100MPa, 120MPa, 140MPa, etc.) and vacuum degree 10 -3 Pa-10 -2 Pa conditions for 30min-150min (such as 50min, 70min, 90min, 100min, 120min, etc.). In one embodiment of the present application, the pressure direction of the hot pressing is parallel to the easy magnetization axis direction of the rare earth permanent magnet blank. The presence of hot pressing pressure in the present application increases the diffusion kinetic energy of the molten diffusion alloy material, which can be distributed between the main phase grains along the grain boundary diffusion channel, improve the orientation degree of the main phase, and improve the remanence, thereby improving the performance of the rare earth permanent magnet.
[0092] In one embodiment of the present application, the diffusion treatment includes heating the sample at 600°C-1000°C (such as 650°C, 700°C, 800°C, 900°C, 950°C, 1000°C, etc.) and vacuum degree 10 -5 Pa-10 -2 Treatment under Pa conditions for 2h-12h (such as 3h, 5h, 7h, 8h, 10h, 11h, etc.) is beneficial to the melting of grain boundary diffusion materials and does not affect the properties of the rare earth permanent magnet blank.
[0093] In one embodiment of the present application, the tempering treatment includes heating the steel sheet at 400°C-600°C (such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.) and vacuum degree 10 -5 Pa-10 -2 Treatment under Pa conditions for 2.5h-10h (such as 3h, 5h, 7h, 8h, 10h, etc.) is beneficial to further homogenize the structure, eliminate defects and improve coercivity.
[0094] In the present application, during the preparation of rare earth permanent magnets, impurities such as oxides, carbides, nitrides, etc. may be introduced to form grain boundary impurity phases.
[0095] In the present application, when the grain boundary diffusion material is placed in sufficient quantity, a grain boundary diffusion layer can be formed on the surface of the rare earth permanent magnet after the diffusion treatment, and the grain boundary diffusion layer can be removed or thinned as needed to obtain the final rare earth permanent magnet. It can be understood that the material of the grain boundary diffusion layer is the grain boundary diffusion material.
[0096] In the present application, the method for preparing a rare earth permanent magnet can prepare the rare earth permanent magnet in any of the above-mentioned embodiments.
[0097] In one embodiment of the present application, the mass content of modified graphene in the shell layer of the main phase of the rare earth permanent magnet is 2.57%-4.91%. Specifically, the mass content of modified graphene in the shell layer of the main phase of the rare earth permanent magnet can be, but is not limited to, 2.57%, 2.73%, 2.89%, 3.05%, 3.27%, 3.45%, 3.7%, 3.91%, 4.3%, 4.56% or 4.8%, etc. In one embodiment, the mass content of modified graphene in the shell layer of the main phase of the rare earth permanent magnet can be 2.7%-4.5%. In another embodiment, the mass content of modified graphene in the shell layer of the main phase of the rare earth permanent magnet can be 3%-4.8%.
[0098] In one embodiment of the present application, the mass content of modified graphene in the grain boundary phase of the rare earth permanent magnet is 2.03%-3.23%. Specifically, the mass content of modified graphene in the grain boundary phase of the rare earth permanent magnet can be, but is not limited to, 2.03%, 2.1%, 2.25%, 2.47%, 2.6%, 2.82%, 2.95%, 3%, 3.15% or 3.2%, etc. In one embodiment, the mass content of modified graphene in the grain boundary phase of the rare earth permanent magnet is 2.2%-3.1%. In another embodiment, the mass content of modified graphene in the grain boundary phase of the rare earth permanent magnet is 2.5%-3%.
[0099] The present application also provides a motor, comprising the rare earth permanent magnet of the first aspect or the rare earth permanent magnet prepared by the preparation method of the second aspect. The permanent magnet drive motor has a long service life and excellent comprehensive performance, and can be applied to the communication technology industry (such as mobile phone vibration motors, speakers, etc.), medical equipment fields (such as nuclear magnetic resonance apparatus, etc.), automotive fields (such as power steering motors, electric vehicle motors), and new energy fields (such as wind turbines, etc.).
[0100] The effects of the technical solution of the present application are further illustrated below through specific examples.
[0101] Example 1
[0102] The formula is Pr 26 Fe 71.9 Co 0.5The raw material of B1 was subjected to belt spinning at a copper roller surface linear speed of 1.1 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 22°C for 1.5 h under a hydrogen pressure of 0.12 MPa, and then dehydrogenated at 510°C for 4.2 h to obtain the first hydrogen powder. Then, 100 parts by weight of the first hydrogen powder was evenly mixed with 0.035 parts by weight of a neodymium iron boron antioxidant (Beijing Juncefeng Technology Development Co., Ltd., brand KM-01), and then ground by a jet mill to obtain a fine powder with an average particle size of 2.1 μm, thereby obtaining the first main phase alloy raw material.
[0103] The formula is La 16 Sm 12 Fe 70 Co 0.5 B 0.9 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.15 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 23°C for 1.6 h under a hydrogen pressure of 0.13 MPa, and then dehydrogenated at 515°C for 4.3 h to obtain a second hydrogen powder. Then, 100 parts by weight of the second hydrogen powder was evenly mixed with 0.04 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 2.2 μm, thereby obtaining a second main phase alloy raw material.
[0104] The formula is La 12 Sm8Fe 66.4 Co1Zr 12 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.2 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 24°C for 1.7 h under a hydrogen pressure of 0.14 MPa, and then dehydrogenated at 520°C for 4.4 h to obtain the third hydrogen powder. Then 100 parts by weight of the third hydrogen powder was evenly mixed with 0.045 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 2.3 μm, thereby obtaining the grain boundary phase alloy raw material.
[0105] 48 parts by weight of the first main phase alloy raw material and 52 parts by weight of the second main phase alloy raw material were uniformly mixed to obtain the main phase alloy powder. 92 parts by weight of the main phase alloy powder and 8 parts by weight of the grain boundary phase alloy powder were uniformly mixed to obtain the rare earth permanent magnet raw material. 100 parts by weight of the rare earth permanent magnet raw material was uniformly mixed with 0.03 parts by weight of gasoline (Haotian Chemical Company, brand YS-06) to obtain the rare earth permanent magnet blank alloy powder.
[0106] The rare earth permanent magnet blank alloy powder was formed in a constant magnetic field of 1.6T, and then kept under 175MPa isostatic pressure for 62s; then sintered at 1035℃ for 4.2h; and then pre-tempered, including primary tempering at 855℃ for 2.5h, and secondary tempering at 482℃ for 3.5h, to obtain the rare earth permanent magnet blank. The rare earth permanent magnet blank was machined into a cuboid with a length of 17mm, a width of 14mm, and a thickness of 2mm.
[0107] The formula is Zn 82.25 Al 16 Si1Ti 0.15 The low melting point zinc alloy is prepared by rapid solidification atomization method, the cooling rate of the gas atomization method is 104K / s, the atomization pressure is 25MPa, and the fine powder with an average particle size of 60nm is obtained to obtain the zinc alloy material. The zinc alloy material is mixed with graphene and placed in a ball mill, and the ball milling is carried out under the protection of inert gas argon, the ball-to-material ratio is 6:1, the rotation speed is 165r / min, and the ball milling time is 7h, and the modified graphene with an average particle size of 15nm is obtained, and the mass content of graphene in the modified graphene is 20%.
[0108] The formula is Pr6Dy 24 Fe 53.4 Al 16 The raw materials are melted at 600°C, and a diffusion alloy ribbon is obtained at a rapid quenching speed of 19 m / s, and then ground by ball milling to obtain a fine powder with an average particle size of 35 nm to obtain a diffusion alloy material. The diffusion alloy material and modified graphene are mixed to obtain a grain boundary diffusion material, and the mass content of the modified graphene in the grain boundary diffusion material is 12%.
[0109] The rare earth permanent magnet blank is sandblasted, and then the grain boundary diffusion material is evenly coated on the upper and lower surfaces of the rare earth permanent magnet blank, and then placed in a hot pressing mold. The hot pressing mold is placed in a vacuum hot pressing furnace at a vacuum degree of 8×10 -2 Pa, the pressing temperature is 550℃, and the hot pressing is carried out under a pressure of 80Mpa, and the temperature and pressure are kept for 30 minutes. The pressure direction is parallel to the easy magnetization axis direction. Then, the vacuum degree is 5×10 -2 Pa, the diffusion temperature was 850℃, and the grain boundary diffusion was carried out for 8h. Then the tempering treatment was carried out, and the tempering temperature was 410℃, the time was 2.5h, and the vacuum degree was 4×10 -2 Pa, and rare earth permanent magnet A1 is obtained. The core composition of the main phase of rare earth permanent magnet A1 is Pr8La 11 Sm8Fe 70.9 Co 0.5 B 0.9 , the shell composition of the main phase is La6Sm 5.2 Pr 3.9Dy 6.7 Fe 63.54 Co 0.2 B 0.28 Zr3Al5Zn 3.8 Si 0.07 Ti 0.01 C 1.6 , the grain boundary phase composition is La5Sm 2.6 Pr 2.2 Dy 9.7 Fe 60.59 Co 0.2 Zr4Al5Zn 7.5 Si 0.09 Ti 0.02 C 2.4 The mass content of rare earth elements in the shell of the main phase is 0.807 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-3.3μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A1 is 22%.
[0110] The rare earth permanent magnet A1 was cut and the cut surface was properly treated. Its microstructure was observed under an electron scanning microscope. The results are as follows: Figure 3 As shown, it can be clearly seen that its main phase is divided into the core ( Figure 3 31) and shell ( Figure 3 32) and the grain boundary phase ( Figure 3 33) isolates and / or encapsulates the adjacent main phase.
[0111] Example 2
[0112] The method is substantially the same as Example 1, except that the rare earth permanent magnet blank is machined into a cuboid with a length of 17 mm, a width of 14 mm, and a thickness of 10 mm. The remaining processes are the same as Example 1 to obtain a rare earth permanent magnet A2. The core composition of the main phase of the rare earth permanent magnet A2 is Pr8La 11 Sm8Fe 70.9 Co 0.5 B 0.9 , the shell composition of the main phase is La6Sm 5.2 Pr 3.9 Dy 6.7 Fe 63.54 Co 0. 2B 0.28 Zr3Al5Zn 3.8 Si 0.07 Ti 0.01 C 1.6 , the grain boundary phase composition is La5Sm 2.6 Pr 2.2 Dy 9.7 Fe 60.59 Co 0.2Zr4Al5Zn 7.5 Si 0.0 9Ti 0.02 C 2.4 The mass content of rare earth elements in the shell of the main phase is 0.807 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 0.6μm-2.7μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A2 is 20%.
[0113] Example 3
[0114] The formula is Nd 28 Fe 68.8 Co 1.5 B 1.1 The raw material was subjected to belt spinning at a copper roller surface linear speed of 2.3 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 24°C for 2.8 hours under a hydrogen pressure of 1.4 MPa, and then dehydrogenated at 648°C for 7.8 hours to obtain the first hydrogen powder. Then, 100 parts by weight of the first hydrogen powder was evenly mixed with 0.12 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 4.3 μm, thereby obtaining the first main phase alloy raw material.
[0115] The formula is Ce 14 G 16 Fe 66.2 Co2B 1.2 The raw material was subjected to belt spinning at a copper roller surface linear speed of 2.4 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 23°C for 2.9 hours under a hydrogen pressure of 1.3 MPa, and then dehydrogenated at 649°C for 7.9 hours to obtain a second hydrogen powder. Then, 100 parts by weight of the second hydrogen powder was evenly mixed with 0.13 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 4.4 μm, thereby obtaining a second main phase alloy raw material.
[0116] The formula is Ce 13 Pr 12 Fe 47.4 Co3Ga 24 The raw material was subjected to belt spinning at a copper roller surface linear speed of 2.5 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 25°C for 3 hours under a hydrogen pressure of 1.5 MPa, and then dehydrogenated at 650°C for 8 hours to obtain the third hydrogen powder. Then 100 parts by weight of the third hydrogen powder was evenly mixed with 0.15 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 4.5 μm, thereby obtaining a grain boundary phase alloy raw material.
[0117] 33 parts by weight of the first main phase alloy raw material and 67 parts by weight of the second main phase alloy raw material were uniformly mixed to obtain the main phase alloy powder. 84 parts by weight of the main phase alloy powder and 16 parts by weight of the grain boundary phase alloy powder were uniformly mixed to obtain the rare earth permanent magnet raw material. 100 parts by weight of the rare earth permanent magnet raw material was uniformly mixed with 0.02 parts by weight of oleic acid (Haotian Chemical Company) to obtain the rare earth permanent magnet blank alloy powder.
[0118] The rare earth permanent magnet blank alloy powder was formed in a constant magnetic field of 3.5T, and then kept under 210MPa isostatic pressure for 150s; then sintered at 1090℃ for 4.5h; and then pre-tempered, including primary tempering at 950℃ for 3h, and then secondary tempering at 520℃ for 4h, to obtain the rare earth permanent magnet blank. The rare earth permanent magnet blank was machined into a cuboid with a length of 14mm, a width of 12mm, and a thickness of 7mm.
[0119] The formula is Zn 62.8 Al 34 Si2Ti 0.6 The low melting point zinc alloy was prepared by rapid solidification atomization method, the cooling rate of the gas atomization method was 105K / s, the atomization pressure was 48MPa, and the fine powder with an average particle size of 78nm was obtained to obtain the zinc alloy material. The zinc alloy material was mixed with graphene and placed in a ball mill, and the ball milling was carried out under the protection of inert gas argon, the ball-to-material ratio was 9:1 at a low speed, the rotation speed was 175r / min, and the ball milling time was 9h, and the modified graphene with an average particle size of 23nm was obtained, and the mass content of graphene in the modified graphene was 37%.
[0120] The formula is Nd 14 Tb 31 Fe 31.4 Ga 23 The raw materials are melted at 850°C, and a diffusion alloy ribbon is obtained at a rapid quenching speed of 26 m / s, and then ground by ball milling to obtain a fine powder with an average particle size of 80 nm to obtain a diffusion alloy material. The diffusion alloy material and modified graphene are mixed to obtain a grain boundary diffusion material, and the mass content of the modified graphene in the grain boundary diffusion material is 22%.
[0121] After pickling the rare earth permanent magnet blank with 0.3wt% nitric acid aqueous solution, the grain boundary diffusion material is evenly coated on the upper and lower surfaces of the rare earth permanent magnet blank, and then placed in a hot pressing mold. The hot pressing mold is placed in a vacuum hot pressing furnace at a vacuum degree of 1×10 -2 Pa, the pressing temperature is 800℃, the hot pressing is carried out under a pressure of 150Mpa, and the temperature and pressure are kept for 150min. The pressure direction is parallel to the easy magnetization axis direction. Then, the vacuum degree is 1×10 -5Pa, the grain boundary diffusion was carried out at a diffusion temperature of 600°C for 12 hours. Then the tempering treatment was carried out at a temperature of 400°C, a time of 10 hours, and a vacuum degree of 1×10 -2 Pa, and rare earth permanent magnet A3 is obtained. The core composition of the main phase of rare earth permanent magnet A3 is Nd 10 Ce 12 Gd8 66.4 Co 1.8 B 1.1 , the shell composition of the main phase is Ce7Gd 8.9 Pr 3.8 T4h 8.8 Fe 41.53 Co 1.9 B 0.45 Ga8Al6Zn 6.3 Si 0.09 Ti 0.03 C 2.5 , the grain boundary phase composition is Ce 7.3 PdX 3.8 Tb 14.5 Fe 30.8 Co 1.7 Ga 14 Al 12 Zn8Si 0.15 Ti 0.05 C4, the mass content of rare earth elements in the shell of the main phase is 1.083 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1.5μm-3μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A3 is 37%.
[0122] Example 4
[0123] The method is substantially the same as Example 3, except that 50 parts by weight of the first main phase alloy raw material and 50 parts by weight of the second main phase alloy raw material are uniformly mixed to obtain the main phase alloy powder, and the remaining processes are the same as Example 3 to obtain the rare earth permanent magnet A4. The core composition of the main phase of the rare earth permanent magnet A4 is Nd 9.93 Ce 8.9 G 10.08 Fe 67.49 Co 1.75 B 1.15 , the shell composition of the main phase is Nd 6.1 Ce 7.18 G 3.2 PcqI 8.7 Fe 47.02 Co 1.72 B 0.46 Ga 8.4 Al 7.2 Zn 4.8 Si 0.09 Ti0.03 C 2.4 , the grain boundary phase composition is Ce 7.3 PdX 3.8 Tb 14.5 Fe 30.8 Co 1.7 Ga 14 Al 12 Zn8Si 0.15 Ti 0.05 C4, the mass content of rare earth elements in the shell of the main phase is 1.093 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1.5μm-2.5μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A4 is 38%.
[0124] Example 5
[0125] The method is substantially the same as Example 3, except that 95 parts by weight of the main phase alloy powder and 5 parts by weight of the grain boundary phase alloy powder are uniformly mixed to obtain a raw material for a rare earth permanent magnet. The remaining processes are the same as those of Example 3 to obtain a rare earth permanent magnet A5. The core composition of the main phase of the rare earth permanent magnet A5 is Nd 10 Ce 12 Gd8 66.4 Co 1.8 B 1.1 , the shell composition of the main phase is Nd 6.94 Ce 7.998 G 3.2 Pr 1.06 Tb 8.742 Fe 49.872 Co 1.458 B 0.44 Ga 12.39 Al 1.54 Si 0.09 Ti 0.03 Zn 2.876 C 2.664 , the grain boundary phase composition is Ce 5.33 Pr 2.92 Nd 3.83 Tb 14.57 Fe 38.77 Co 1.23 Ga 20.65 Al 2.57 Si 0.15 Ti 0.045 Zn 4.79 C 4.44 The mass content of rare earth elements in the shell of the main phase is 1.028 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-2μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A5 is 36%.
[0126] Example 6
[0127] The formula is Pr 27 Fe 70.35 Co1B 1.05 The raw material is subjected to belt spinning at a copper roller surface linear speed of 1 m / s, and the resulting belt spinning sheet is subjected to hydrogen absorption at 15°C for 3 hours under a hydrogen pressure of 0.1 MPa, and then dehydrogenated at 500°C for 8 hours to obtain the first hydrogen powder. Then, 100 parts by weight of the first hydrogen powder is evenly mixed with 0.03 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 2 μm, thereby obtaining the first main phase alloy raw material.
[0128] The formula is La 12 Ho 17 Fe 68.4 The raw material of Co1B1 was subjected to belt spinning at a copper roller surface linear speed of 1.9 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 25°C for 1 hour under a hydrogen pressure of 1.5 MPa, and then dehydrogenated at 650°C for 4 hours to obtain a second hydrogen powder. Then, 100 parts by weight of the second hydrogen powder was evenly mixed with 0.15 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 4.5 μm, thereby obtaining a second main phase alloy raw material.
[0129] The formula is Ce 10 Nd 12 Fe 60.4 Co2Cu 15 The raw material was subjected to belt spinning at a copper roller surface linear speed of 2.5 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 22°C for 1.5 hours under a hydrogen pressure of 1.2 MPa, and then dehydrogenated at 600°C for 5 hours to obtain a third hydrogen powder. Then, 100 parts by weight of the third hydrogen powder was uniformly mixed with 0.14 parts by weight of a neodymium iron boron antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 4 μm, thereby obtaining a grain boundary phase alloy raw material.
[0130] 45 parts by weight of the first main phase alloy raw material and 55 parts by weight of the second main phase alloy raw material were uniformly mixed to obtain the main phase alloy powder. 86 parts by weight of the main phase alloy powder and 14 parts by weight of the grain boundary phase alloy powder were uniformly mixed to obtain the rare earth permanent magnet raw material. 100 parts by weight of the rare earth permanent magnet raw material and 0.2 parts by weight of stearic acid glyceryl ester (Haotian Chemical Company) were uniformly mixed to obtain the rare earth permanent magnet blank alloy powder.
[0131] The rare earth permanent magnet blank alloy powder was formed in a constant magnetic field of 1.5T, and then kept under 170MPa isostatic pressure for 60s; then sintered at 1030℃ for 5.5h; and then pre-tempered, including primary tempering at 850℃ for 5h, and secondary tempering at 480℃ for 8h, to obtain the rare earth permanent magnet blank. The rare earth permanent magnet blank was machined into a cuboid with a length of 16mm, a width of 14mm, and a thickness of 5mm.
[0132] The formula is Zn 79.5 Al 18 Si 1.5 Ti 0.4 The low melting point zinc alloy was prepared by rapid solidification atomization method, the cooling rate of the gas atomization method was 103K / s, the atomization pressure was 45MPa, and the fine powder with an average particle size of 65nm was obtained to obtain the zinc alloy material. The zinc alloy material was mixed with graphene and placed in a ball mill, and the ball milling was carried out under the protection of inert gas argon, the ball-to-material ratio was 7:1 at a low speed, the rotation speed was 170r / min, and the ball milling time was 8h, and the modified graphene with an average particle size of 20nm was obtained, and the mass content of graphene in the modified graphene was 29%.
[0133] The formula is Pr 10 Dy 25 Fe 45.4 Cu 19 The raw materials are melted at 620°C, and a diffusion alloy ribbon is obtained at a rapid quenching speed of 20 m / s, and then ground by ball milling to obtain a fine powder with an average particle size of 40 nm to obtain a diffusion alloy material. The diffusion alloy material and modified graphene are mixed to obtain a grain boundary diffusion material, and the mass content of the modified graphene in the grain boundary diffusion material is 20%.
[0134] After pickling the rare earth permanent magnet blank with 0.3wt% nitric acid aqueous solution, the grain boundary diffusion material is evenly coated on the upper and lower surfaces of the rare earth permanent magnet blank, and then placed in a hot pressing mold. The hot pressing mold is placed in a vacuum hot pressing furnace at a vacuum degree of 1×10 -3 Pa, the pressing temperature is 560℃, the hot pressing is carried out under a pressure of 90Mpa, and the temperature and pressure are kept for 40min. The pressure direction is parallel to the easy magnetization axis direction. Then, the vacuum degree is 1×10 -2 Pa, the diffusion temperature is 1000℃, the grain boundary diffusion is carried out for 2h. Then the tempering treatment is carried out, the tempering temperature is 600℃, the time is 5h, the vacuum degree is 1×10 -5 Pa, and rare earth permanent magnet A6 is obtained. The core composition of the main phase of rare earth permanent magnet A6 is Pr9La 13 Ho 7.5 Fe 67.8Co1B1, the shell composition of the main phase is Pr4Ho5La2Ce3Nd4Dy7Fe 55.8 Co1B 0.4 Cu4Al7Zn4Si 0.08 Ti 0.02 C2, grain boundary phase composition is Ce5Nd3Pr 3.79 Dy 10 Fe 55.38 Co1Cu4Al6Zn8Si 0.1 Ti 0.03 C3, the mass content of rare earth elements in the shell of the main phase is 0.847 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-2μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A6 is 25%.
[0135] Example 7
[0136] The formula is Nd 25.5 Fe 73 B 0.9 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.5 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 20°C for 1.2 h under a hydrogen pressure of 1.2 MPa, and then dehydrogenated at 531°C for 5 h to obtain the first hydrogen powder. Then, 100 parts by weight of the first hydrogen powder was evenly mixed with 0.05 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 2.5 μm, thereby obtaining the first main phase alloy raw material.
[0137] The formula is Ce 11 Y 16.5 Fe 71.1 B 0.8 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.9 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 23°C for 1.5 h under a hydrogen pressure of 1.3 MPa, and then dehydrogenated at 523°C for 5.2 h to obtain a second hydrogen powder. Then, 100 parts by weight of the second hydrogen powder was evenly mixed with 0.051 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 2.6 μm, thereby obtaining a second main phase alloy raw material.
[0138] The formula is Ce 10 Sm9Fe 70.4 Sn 10The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.7 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 24°C for 1.3 h under a hydrogen pressure of 1.4 MPa, and then dehydrogenated at 525°C for 5.3 h to obtain the third hydrogen powder. Then 100 parts by weight of the third hydrogen powder was evenly mixed with 0.052 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 2.7 μm, thereby obtaining the grain boundary phase alloy raw material.
[0139] 46 parts by weight of the first main phase alloy raw material and 54 parts by weight of the second main phase alloy raw material were uniformly mixed to obtain the main phase alloy powder. 93 parts by weight of the main phase alloy powder and 7 parts by weight of the grain boundary phase alloy powder were uniformly mixed to obtain the rare earth permanent magnet raw material. 100 parts by weight of the rare earth permanent magnet raw material were uniformly mixed with 0.05 parts by weight of dehydrated sorbitol (Haotian Chemical Company) to obtain the rare earth permanent magnet blank alloy powder.
[0140] The rare earth permanent magnet blank alloy powder was formed in a 2T constant magnetic field, and then kept under 180MPa isostatic pressure for 100s; then sintered at 1080℃ for 4h; and then pre-tempered, including primary tempering at 860℃ for 3h, and then secondary tempering at 490℃ for 4h, to obtain a rare earth permanent magnet blank. The rare earth permanent magnet blank was machined into a cuboid with a length of 15mm, a width of 11mm, and a thickness of 10mm.
[0141] The formula is Zn 84.27 Al 14.1 Si 0.9 Ti 0.13 The low melting point zinc alloy was prepared by rapid solidification atomization method, the cooling rate of the gas atomization method was 105K / s, the atomization pressure was 20MPa, and the fine powder with an average particle size of 58nm was obtained to obtain the zinc alloy material. The zinc alloy material was mixed with graphene and placed in a ball mill, and the ball milling was carried out under the protection of inert gas argon, the ball-to-material ratio was 5:1 at a low speed, the rotation speed was 160r / min, and the ball milling time was 6h, and the modified graphene with an average particle size of 10nm was obtained, and the mass content of graphene in the modified graphene was 19%.
[0142] The formula is Nd 5.2 Tb 23.8 Fe 54.9 Sn 15.5 The raw materials are melted at 650°C, and a diffusion alloy ribbon is obtained at a rapid quenching speed of 18 m / s, and then ground by ball milling to obtain a fine powder with an average particle size of 30 nm to obtain a diffusion alloy material. The diffusion alloy material and modified graphene are mixed to obtain a grain boundary diffusion material, and the mass content of the modified graphene in the grain boundary diffusion material is 10%.
[0143] After pickling the rare earth permanent magnet blank with 0.3wt% nitric acid aqueous solution, the grain boundary diffusion material is evenly coated on the upper and lower surfaces of the rare earth permanent magnet blank, and then placed in a hot pressing mold. The hot pressing mold is placed in a vacuum hot pressing furnace at a vacuum degree of 5×10 -2 Pa, the pressing temperature is 570℃, the hot pressing is carried out under a pressure of 100Mpa, and the temperature and pressure are kept for 100min. The pressure direction is parallel to the easy magnetization axis direction. Then, the vacuum degree is 5×10 -3 Pa, the grain boundary diffusion was carried out at a diffusion temperature of 700°C for 6.5 hours. Then the tempering treatment was carried out at a temperature of 450°C, a time of 7.5 hours, and a vacuum degree of 8×10 -3 Pa, and rare earth permanent magnet A7 is obtained. The core composition of the main phase of rare earth permanent magnet A7 is Nd 7.91 Ce 10 Y 8.98 Fe 71.58 B 0.83 The shell composition of the main phase is Sm2Ce4Y 5.15 Nd 3.83 Tb 6.66 Fe 64.2439 B 0.25 Sn5Al4Zn 2.5 Si 0.061 Ti 0.0091 C 1.596 , the grain boundary phase composition is Ce3Sm 4.79 Nd 2.08 Tb 9.52 Fe 61.095 Sn 5.435 Al7Zn4Si 0.087 Ti 0.013 C 2.28 The mass content of rare earth elements in the shell of the main phase is 0.805 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 0.1μm-1μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A7 is 20%.
[0144] Example 8
[0145] The formula is Pr 29.5 Fe 66.7 Co2B 1.2 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.8 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 15°C for 1.8 hours under a hydrogen pressure of 1.2 MPa, and then dehydrogenated at 508°C for 7 hours to obtain the first hydrogen powder. Then, 100 parts by weight of the first hydrogen powder was evenly mixed with 0.1 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 3.9 μm, thereby obtaining the first main phase alloy raw material.
[0146] The formula is Gd 14 Y 17.5 Fe 64.15 Co 2.5 B 1.25 The raw material was subjected to belt spinning at a copper roller surface linear speed of 1.9 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 17°C for 1.9 h under a hydrogen pressure of 1.4 MPa, and then dehydrogenated at 509°C for 7.2 h to obtain a second hydrogen powder. Then, 100 parts by weight of the second hydrogen powder was evenly mixed with 0.12 parts by weight of a NdFeB antioxidant, and then ground by a jet mill to obtain a fine powder with an average particle size of 4.2 μm, thereby obtaining a second main phase alloy raw material.
[0147] The formula is La 13 Ce 12.2 Fe 45.2 Co4Sn4Al6Zn 15 The raw material was subjected to belt spinning at a copper roller surface linear speed of 2 m / s, and the resulting belt spinning sheet was subjected to hydrogen absorption at 19°C for 2 hours under a hydrogen pressure of 1.5 MPa, and then dehydrogenated at 511°C for 7.3 hours to obtain the third hydrogen powder. Then 100 parts by weight of the third hydrogen powder was evenly mixed with 0.13 parts by weight of NdFeB antioxidant, and then ground by air jet mill to obtain fine powder with an average particle size of 4.5 μm, thereby obtaining a grain boundary phase alloy raw material.
[0148] 33 parts by weight of the first main phase alloy raw material and 67 parts by weight of the second main phase alloy raw material were uniformly mixed to obtain the main phase alloy powder. 84 parts by weight of the main phase alloy powder and 16 parts by weight of the grain boundary phase alloy powder were uniformly mixed to obtain the rare earth permanent magnet raw material. 100 parts by weight of the rare earth permanent magnet raw material was uniformly mixed with 0.02 parts by weight of stearic acid (Haotian Chemical Company) to obtain the rare earth permanent magnet blank alloy powder.
[0149] The rare earth permanent magnet blank alloy powder was formed in a constant magnetic field of 2.5T, and then kept under 205MPa isostatic pressure for 130s; then sintered at 1085℃ for 4h; and then pre-tempered, including primary tempering at 875℃ for 4h, and secondary tempering at 515℃ for 7h, to obtain the rare earth permanent magnet blank. The rare earth permanent magnet blank was machined into a cuboid with a length of 17mm, a width of 8mm, and a thickness of 10mm.
[0150] The formula is Zn 62.1 Al 34.4 Si 2.2 Ti 0.7The low melting point zinc alloy is prepared by rapid solidification atomization method, the cooling rate of the gas atomization method is 103K / s, the atomization pressure is 50MPa, and the fine powder with an average particle size of 80nm is obtained to obtain the zinc alloy material. The zinc alloy material is mixed with graphene and placed in a ball mill, and the ball milling is carried out under the protection of inert gas argon, the ball-to-material ratio is 10:1, the rotation speed is 180r / min, and the ball milling time is 10h, and the modified graphene with an average particle size of 25nm is obtained, and the mass content of graphene in the modified graphene is 38%.
[0151] The formula is Pr 14.5 Dy 31.8 Fe 29.1 Sn 10 Zn 14 The raw materials are melted at 670°C, and a diffusion alloy ribbon is obtained at a rapid quenching speed of 27 m / s, and then ground by ball milling to obtain a fine powder with an average particle size of 85 nm to obtain a diffusion alloy material. The diffusion alloy material and modified graphene are mixed to obtain a grain boundary diffusion material, and the mass content of the modified graphene in the grain boundary diffusion material is 23%.
[0152] After pickling the rare earth permanent magnet blank with 0.3wt% nitric acid aqueous solution, the grain boundary diffusion material is evenly coated on the upper and lower surfaces of the rare earth permanent magnet blank, and then placed in a hot pressing mold. The hot pressing mold is placed in a vacuum hot pressing furnace at a vacuum degree of 9×10 -2 Pa, the pressing temperature was 575℃, and the hot pressing was carried out under a pressure of 87Mpa, and the temperature and pressure were kept for 45 minutes. The pressure direction was parallel to the easy magnetization axis. Then, the vacuum degree was 7×10 -2 Pa, the diffusion temperature was 915℃, the grain boundary diffusion was carried out for 4h. Then the tempering treatment was carried out, the tempering temperature was 474℃, the time was 4.7h, the vacuum degree was 9×10 -3 Pa, and rare earth permanent magnet A8 is obtained. The core composition of the main phase of rare earth permanent magnet A8 is Pr 10.03 G 15 Y 5.79 Fe 64.92 Co 2.33 B 1.23 , the shell composition of the main phase is La5Ce 4.57 Y3P 8.1 Dy 8.97 Fe 40.784 Co 2.1 B 0.49 Sn4Al 10 Zn 6.4208 Si 0.098 Ti 0.0312 C 2.736 , the grain boundary phase composition is La5Ce 7.096 Pr6.815 Dy 14.946 Fe 24.97 Co 1.92 Sn7Al 12.777 Zn 14 Si 0.164 Ti 0.052 C 4.56 The mass content of rare earth elements in the shell of the main phase is 1.059 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 6μm-8.5μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A8 is 40%.
[0153] Example 9
[0154] The method is substantially the same as Example 1, except that 60 parts by weight of the first main phase alloy raw material and 40 parts by weight of the second main phase alloy raw material are uniformly mixed to obtain the main phase alloy powder, and 97 parts by weight of the main phase alloy powder and 3 parts by weight of the grain boundary phase alloy powder are uniformly mixed to obtain the rare earth permanent magnet raw material. The remaining processes are the same as Example 1 to obtain the rare earth permanent magnet A9. The core composition of the main phase of the rare earth permanent magnet A9 is Pr 8.93 7S 13.48 Fe 68.86 Co 0.2 B 0.835 , the shell composition of the main phase is La 5.66 Sm 5.43 Pr 4.83 Dy 8.61 Fe 60.08 Co 0.067 B 0.28 Zr 2.28 Al 5.36 Zn 4.29 Si 0.067 Ti 0.0094 C 2.35 , the grain boundary phase composition is La5Sm 1.46 Pr 2.81 Dy 12.85 Fe 55.66 Co 0.1 Zr 3.4 Al8Zn 6.41 Si 0.1 Ti 0.014 C 3.5 The mass content of rare earth elements in the shell of the main phase is 0.834 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 0.6μm-1.8μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A9 is 15%.
[0155] Example 10
[0156] The method is substantially the same as Example 1, except that 25 parts by weight of the first main phase alloy raw material and 75 parts by weight of the second main phase alloy raw material are uniformly mixed to obtain the main phase alloy powder, and 80 parts by weight of the main phase alloy powder and 20 parts by weight of the grain boundary phase alloy powder are uniformly mixed to obtain the rare earth permanent magnet raw material. The remaining processes are the same as Example 1 to obtain the rare earth permanent magnet A10. The core composition of the main phase of the rare earth permanent magnet A10 is Pr 9.69 8S 11.53 Fe 66.54 Co 2.31 B 1.23 , the shell composition of the main phase is La 7.89 Sm 7.11 Pr 5.77 Dy 8.4 Fe 53.04 Co 0.7 B 0.25 Zr 5.36 Al 5.68 Zn 2.28 Si 0.088 Ti 0.03 C 2.72 , the grain boundary phase composition is La 7.86 Sm6 4.79 Dy 10.49 Fe 49.66 Co 0.3 Zr 6.7 Al 7.1 Zn 2.85 Si 0.11 Ti 0.038 C 3.4 The mass content of rare earth elements in the shell of the main phase is 1 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 6.2μm-8.7μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A10 is 41%.
[0157] Embodiment 11
[0158] It is similar to Example 1, except that the formula is Pr8Nd 18 Fe 71.9 Co 0.5 The raw material of the first main phase alloy is prepared by using the raw material of B1. 20 Tb4Fe 53.4 Al 16 The rest of the process is the same as in Example 1 to obtain a rare earth permanent magnet A11. The core composition of the main phase of the rare earth permanent magnet A11 is Pr 2.72 Nd 6.12 La 11.06 Sm 7.94 Fe 70.026 Co0.5 B 0.934 , the shell composition of the main phase is La 7.18 Sm 5.14 Nd 4.14 Pr 1.09 Dy 5.64 Tb 1.13 Fe 59.51 Co 0.45 Zr 2.95 Al 5.24 Zn 3.76 Si 0.045 Ti 0.007 C 2.66 B 0.37 , the grain boundary phase composition is La 4.92 Sm 3.28 Nd 2.82 Dy 9.4 Tb 1.88 Fe 52.15 Co 0.41 Zr 4.92 Al 8.73 Zn 6.26 Si 0.076 Ti 0.01 C 4.44 The mass content of rare earth elements in the shell of the main phase is 0.89 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1.5μm-3.5μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A1 is 23%.
[0159] Example 12
[0160] The formula is Pr 29.4 Fe 66.83 Co 1.98 B 1.19 The first main phase alloy raw material is obtained by the process of Example 1. 11 Sm 20.4 Fe 64.29 Co 2.47 B 1.24 The raw materials of the second main phase alloy are obtained by the process of Example 1. 10 Sm 9.6 Fe 52.1 Co 3.7 Zr 24 The raw materials of the first main phase alloy are uniformly mixed with 28 parts by weight of the first main phase alloy raw material and 72 parts by weight of the second main phase alloy raw material to obtain the main phase alloy powder. 98 parts by weight of the main phase alloy powder and 2 parts by weight of the grain boundary phase alloy powder are uniformly mixed to obtain the rare earth permanent magnet raw material.
[0161] The formula is Zn 62.75Al 34 Si2Ti 0.65 The zinc alloy material is obtained by the process of Example 1. The modified graphene is obtained by the process of Example 1, and the mass content of graphene in the modified graphene is 15%. 5.5 Dy 24 Fe 53.9 Al 16 The raw materials are used to obtain a diffusion alloy material according to the process of Example 1. The diffusion alloy material and the modified graphene are mixed to obtain a grain boundary diffusion material, wherein the mass content of the modified graphene in the grain boundary diffusion material is 5%.
[0162] The rare earth permanent magnet A12 is obtained according to the process of Example 1. The core composition of the main phase of the rare earth permanent magnet A12 is Pr 10.0 3La 10 Sm 10.79 Fe 64.92 Co 2.33 B 1.23 , the shell composition of the main phase is La 5.15 Sm6 3.83 Dy 6.66 Fe 63.89 Co 0.35 B 0.25 Zr5Al4Zn 2.5 Si 0.061 Ti 0.0091 C 1.596 , the grain boundary phase composition is La4Sm 3.79 Pr 2.08 Dy 9.52 Fe 60.795 Co 0.3 Zr 5.435 Al7Zn4Si 0.087 Ti 0.013 C 2.28 The mass content of rare earth elements in the shell of the main phase is 0.702 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 0.2μm-2.3μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A12 is 12%.
[0163] Example 13
[0164] The formula is Pr 25.6 Fe 72.82 B 0.98 The first main phase alloy raw material is obtained by the process of Example 1. 17 Sm 10.6 Fe 70.98 B 0.82 The raw materials of the second main phase alloy are obtained by the process of Example 1. 12 Sm13 Fe 62.9 Co 0.5 Zr 11 The raw materials of the first main phase alloy are uniformly mixed with 53 parts by weight of the first main phase alloy raw material and 47 parts by weight of the second main phase alloy raw material to obtain the main phase alloy powder. 73 parts by weight of the main phase alloy powder and 27 parts by weight of the grain boundary phase alloy powder are uniformly mixed to obtain the rare earth permanent magnet raw material.
[0165] The formula is Zn 83.75 Al 14.5 Si1Ti 0.15 The zinc alloy material is obtained by the process of Example 1. The modified graphene is obtained by the process of Example 1, and the mass content of graphene in the modified graphene is 40%. 14.4 Dy 31.5 Fe 30.5 Al 23 The raw materials are used to obtain a diffusion alloy material according to the process of Example 1. The diffusion alloy material and the modified graphene are mixed to obtain a grain boundary diffusion material, wherein the mass content of the modified graphene in the grain boundary diffusion material is 27%.
[0166] The rare earth permanent magnet A13 is obtained according to the process of Example 1. The core composition of the main phase of the rare earth permanent magnet A13 is Pr 7.91 La 8.98 Sm 10 Fe 71.58 B 0.83 , the shell composition of the main phase is La 10 Sm 5.57 Pr 8.1 Dy 8.97 Fe 41.184 Co 2.1 B 0.49 Zr 8.18 Al5Zn7Si 0.098 Ti 0.031 C 2.736 , the grain boundary phase composition is La7Sm 5.096 Pr 6.815 Dy 14.946 Fe 24.97 Co 1.92 Zr 9.5 Al 10.305 Zn 14 Si 0.164 Ti 0.052 C 4.56 The mass content of rare earth elements in the shell of the main phase is 1.214 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 5μm-8.3μm, and the mass content of the grain boundary phase in the rare earth permanent magnet A13 is 42%.
[0167] Comparative Example 1
[0168] The rare earth permanent magnet blank prepared in Example 1 is directly used as the rare earth permanent magnet CA1 of Comparative Example 1.
[0169] Comparative Example 2
[0170] The same as Example 1, except that the first main phase alloy raw material, the second main phase alloy raw material, and the grain boundary phase alloy raw material are not used, and a single alloy raw material is directly prepared into a rare earth permanent magnet blank, and its composition is La 8.61 Sm 6.38 Nd 11.48 Fe 71.15 Co 0.54 B 0.87 Zr 0.96 The remaining processes are the same as those in Example 1 to produce a rare earth permanent magnet CA2.
[0171] Comparative Example 3
[0172] The same as Example 1, except that the formula is Pr 9.6 Nd 29.3 Dy 10 Fe 15.5 Co 16.5 B 0.96 Al 5.5 Cu 3.2 Zr 2.4 The raw material of Ga7 was subjected to a belt spinning process at a copper roller surface linear velocity of 1.4 m / s to serve as a grain boundary phase alloy raw material. The remaining processes were the same as those in Example 1 to produce a rare earth permanent magnet CA3.
[0173] Comparative Example 4
[0174] The method is similar to Example 1, except that the diffusion alloy material is directly used as the grain boundary diffusion material without adding modified graphene to obtain the rare earth permanent magnet CA4. The core composition of the main phase of the rare earth permanent magnet CA4 is Pr8La 11 Sm8Fe 71 Co 0.5 B 0.9 , the shell composition of the main phase is La 8.245 Sm 5.76 Pr 4.877 Dy 6.709 Fe 65.206 Co 0.52 B 0.36 Al 4.47 Zr 3.845 , the grain boundary phase composition is La 6.4 Sm 4.27 Pr 2.795Dy 11.18 Fe 60.375 Co 0.53 Al 7.45 Zr 6.4 The mass content of rare earth elements in the shell of the main phase is 0.948 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-3μm, and the mass content of the grain boundary phase in the rare earth permanent magnet CA4 is 20%.
[0175] Comparative Example 5
[0176] The method is similar to Example 1, except that modified graphene with an average particle size of 11 nm is directly used as the grain boundary diffusion material without adding diffusion alloy material to obtain rare earth permanent magnet CA5. The core composition of the main phase of rare earth permanent magnet CA5 is Pr8La 11 Sm8Fe 70.9 Co 0.5 B 0.9 , the shell composition of the main phase is La 9.97 Sm 7.275 Pr 3.2 Fe 59.74 Co 0.66 Zr 5.57 Al 1.74 Si 0.11 Ti 0.016 Zn9C 2.72 , the grain boundary phase composition is La 9.28 Sm 6.19 Fe 51.83 Co 0.77 Zr 9.28 Al 2.9 Si 0.18 Ti 0.027 Zn 15 C 4.53 The mass content of rare earth elements in the shell of the main phase is 0.757 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-2.5μm, and the mass content of the grain boundary phase in the rare earth permanent magnet CA5 is 18%.
[0177] Comparative Example 6
[0178] The method is similar to Example 1, except that graphene with an average particle size of 11 nm is directly used as a grain boundary diffusion material to produce a rare earth permanent magnet CA6. The core composition of the main phase of the rare earth permanent magnet CA6 is Pr8La 11 Sm8Fe 70.9 Co 0.5 B 0.9 , the shell composition of the main phase is La 9.97 Sm 6.91 Pr 3.2 Fe59.74 Co 0.66 B 0.36 Zr 5.57 C 13.58 , the grain boundary phase composition is La 9.28 Sm 6.19 Fe 51.83 Co 0.77 Zr 9.28 C 22.64 The mass content of rare earth elements in the shell of the main phase is 0.744 times the mass content of rare earth elements in the core of the main phase, the thickness of the shell is 1μm-2.5μm, and the mass content of the grain boundary phase in the rare earth permanent magnet CA6 is 18%.
[0179] Performance Testing
[0180] Remanence and coercivity testing: According to the GB / T 3217-1992 testing standard, the residual magnetic induction intensity (Br) and intrinsic coercivity (Hcj) of the rare earth permanent magnets prepared in the above embodiments and comparative examples were tested at 22°C using NIM-10000H of the Chinese Academy of Metrology.
[0181] High temperature external field durability test: The rare earth permanent magnets (size 33.5mm×13.9mm×5mm) prepared in the above embodiments and comparative examples were subjected to a 7kOe reverse magnetic field, kept at 180°C for 100h, and then cooled to 22°C. A fluxmeter was used to test the irreversible loss of magnetic flux (hirr) of each sample.
[0182] Bending strength test: According to the GBT228.1-2010 test standard, the bending strength of the rare earth permanent magnets prepared in the above embodiments and comparative examples was tested at 25°C using a microcomputer-controlled electronic universal testing machine CMT5105.
[0183] The above performance test results are shown in Table 1. It can be seen that CA1 has not been diffused and modified by grain boundary diffusion materials, and its intrinsic coercive force, anti-demagnetization ability and flexural strength are poor. Compared with CA1, the intrinsic coercive force of A1-A13 is increased by 61% at most, the irreversible loss of magnetic flux is improved by 74.7% at most, and the flexural strength is increased by 55.3% at most. CA2 is made of a single alloy raw material, and CA3 is made of different grain boundary phase alloy raw materials. Its intrinsic coercive force, flexural strength and anti-demagnetization ability are still at a low level; compared with CA2, the intrinsic coercive force of A1 is increased by 76.6%, the irreversible loss of magnetic flux is improved by 74.4%, and the flexural strength is increased by 52.7%. CA4 uses diffusion alloy material as grain boundary diffusion material, and its flexural strength is still at a low level. CA5 directly places modified graphene on the surface of rare earth permanent magnet blank. Although it can improve its flexural strength, it still cannot improve its intrinsic coercive force and anti-demagnetization ability. CA6 directly places graphene on the surface of the rare earth permanent magnet blank, and it is difficult for graphene to enter the interior of the rare earth permanent magnet blank, so the improvement of its bending strength is very limited, and it is also unable to improve its intrinsic coercive force and anti-demagnetization ability. Compared with CA1-CA6, the intrinsic coercive force, anti-demagnetization ability and bending strength of the rare earth permanent magnets of A1-A13 are at a higher level, with excellent comprehensive performance, which is conducive to the use of rare earth permanent magnets.
[0184] Table 1 Performance test results
[0185] Sample No. Br(kGs) Hcj(kOe) Flexural strength(MPa) Hirr (%) A1 12.98 29.83 394 5.84 A2 13 29.9 396 5.53 A3 12.99 29.32 370 5.96 A4 12.95 28.62 364 6.64 A5 12.92 28.71 366 6.8 A6 12.91 29.74 384 6 A7 12.83 27.86 346 10.96 A8 12.76 27.79 350 10.32 A9 12.87 27.95 362 7.47 A10 12.77 27.63 355 9.8 A11 12.9 28.23 382 6.08 A12 12.75 26.5 332 11.1 A13 12.7 27.5 340 11.78 CA1 13.09 18.57 255 21.9 CA2 12.98 16.89 258 22.8 CA3 12.87 20.91 237 21.5 CA4 12.78 25.72 285 12.9 CA5 13.01 20.95 309 13.36 CA6 13.03 19.15 272 13.68
[0186] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A rare earth permanent magnet, characterized in that: The rare earth permanent magnet comprises a main phase and a grain boundary phase, wherein the main phase is dispersed in the grain boundary phase, the main phase comprises a core and a shell layer covering the core, and the shell layer and the grain boundary phase have graphene. The kernel includes RL 1 a RH 1 b Fe c Co d B e , RL 1 Contains at least one of Pr and Nd, RH 1 It includes at least one of La, Ce, Sm, Gd, Ho and Y, a, b, c, d, e are weight parts, 7.91≤a≤10.03, 18.98≤b≤20.79, 64.72≤c≤72.28, 0≤d≤2.33, 0.83≤e≤1.23, The shell includes RL 2 f RL 3 g RH 2 h Fe i Co j B k M 1 l C m , RL 2 Including at least one of La, Ce, Sm, Gd, Ho and Y, RL 3 Contains at least one of Pr and Nd, RH 2 including at least one of Dy and Tb, M 1 Including at least one of Zr, Ga, Cu and Sn and Al, Zn, Si and Ti, f, g, h, i, j, k, l, m are weight parts, 21.64≤f+g+h≤32.64, 3.83≤g≤8.1, 6.66≤h≤8.97, 40.554≤i≤65.014, 0≤j≤2.1, 0.25≤k≤0.49, 11.5≤l≤20.58, 1.596≤m≤2.736, The grain boundary phase includes RL 4 o RL 5 p RH 3 q Fe r Co s M 2 t C u , RL 4 Contains at least one of La, Ce and Sm, RL 5 Contains at least one of Pr and Nd, RH 3 including at least one of Dy and Tb, M 2 It includes at least one of Zr, Ga, Cu and Sn, and Al, Zn, Si and Ti, o, p, q, r, s, t, u are weight parts, and 19.39≤o+p+q≤33.857, 2.08≤p≤6.815, 9.52≤q≤14.946, 24.458≤r≤61.895, 0≤s≤1.92, 16.435≤t≤34.305, 2.28≤u≤4.
56.
2. The rare earth permanent magnet according to claim 1, characterized in that: In the kernel, 8≤a≤10, 19≤b≤20.5, 65.7≤c≤71, 0.5≤d≤1.8, and 0.9≤e≤1.
1.
3. The rare earth permanent magnet according to claim 1, characterized in that: In the shell layer, 21.8≤f+g+h≤32.5, 3.9≤g≤7.8, 6.7≤h≤8.8, 42.5≤i≤63.72, 0.2≤j≤1.9, 0.28≤k≤0.45, 11.8≤l≤20.3, and 1.6≤m≤2.
5.
4. The rare earth permanent magnet according to claim 1, characterized in that: In the grain boundary phase, 19.5≤o+p+q≤33.5, 2.2≤p≤6.7, 9.7≤q≤14.5, 25.7≤r≤60.8, 0.2≤s≤1.7, 16.5≤t≤34, and 2.4≤u≤4.
5. The rare earth permanent magnet according to claim 1, characterized in that: The ratio of the mass content of the rare earth elements in the shell layer to the mass content of the rare earth elements in the core layer is (0.744-1.093):
1.
6. The rare earth permanent magnet according to claim 1, characterized in that: The thickness of the shell layer is 0.1 μm-8.5 μm.
7. The rare earth permanent magnet according to claim 1, characterized in that: The mass content of the grain boundary phase in the rare earth permanent magnet is 20%-40%, and the mass content of the main phase is 60%-80%.
8. A method for preparing a rare earth permanent magnet, characterized in that: include: The first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material are mixed, and the raw material is pressed and sintered to obtain a rare earth permanent magnet blank, wherein the first main phase alloy raw material includes R 1 a' Fe b' Co c' B d' , R 1 The second main phase alloy raw material includes at least one of Pr and Nd, a', b', c', d' are weight parts, 25.5≤a'≤29.5, 66.4≤b'≤73.6, 0≤c'≤2, 0.9≤d'≤1.2, and the second main phase alloy raw material includes R 2 e' Fe f' Co g' B h' , R 2 The alloy comprises at least one of La, Ce, Sm, Gd, Ho and Y, wherein e', f', g' and h' are weight percentages, 27.5≤e'≤31.5, 63.85≤f'≤71.7, 0≤g'≤2.5, 0.8≤h'≤1.25, and the grain boundary phase alloy raw material comprises R 3 i' Fe j' Co k' M 3 l' , R 3 Includes at least one of La, Ce, Sm, Pr and Nd, M 3 It includes at least one of Zr, Ga, Cu, Sn, Al and Zn, i', j', k', l' are weight parts, 19≤i'≤25.2, 44.9≤j'≤71, 0≤k'≤4, 10≤l'≤25; The grain boundary diffusion material is arranged on the surface of the rare earth permanent magnet blank, wherein the grain boundary diffusion material comprises a diffusion alloy material and modified graphene, wherein the modified graphene comprises graphene and a zinc alloy layer covering the graphene, and wherein the diffusion alloy material comprises R 4 m' R 5 n' Fe o' M 4 p' , R 4 Contains at least one of Pr and Nd, R 5 including at least one of Dy and Tb, M 4 The zinc alloy layer comprises at least one of Ga, Cu, Sn, Al and Zn, wherein m', n', o' and p' are weight percentages, 5.2≤m'≤14.5, 23.8≤n'≤31.8, 28.85≤o'≤55.5, 15.5≤p'≤24, and the zinc alloy layer comprises Zn q' Al r' Si s' Ti t' , q', r', s', t' are weight parts, 61.8≤q'≤84.87, 14.1≤r'≤34.4, 0.9≤s'≤2.2, 0.13≤t'≤0.7; The rare earth permanent magnet is obtained after hot pressing, diffusion treatment and tempering treatment.
9. The preparation method according to claim 8, characterized in that: Before the grain boundary diffusion material is arranged on the surface of the rare earth permanent magnet blank, the method further comprises: The graphene is mixed with a zinc alloy material, and the modified graphene is obtained after ball milling.
10. The preparation method according to claim 9, characterized in that: The average particle size of the zinc alloy material is 58nm-80nm; The average particle size of the modified graphene is 10nm-25nm.
11. The preparation method according to claim 9, characterized in that: The ball-to-material ratio in the ball mill is (5-10):1, the rotation speed is 160r / min-180r / min, and the time is 6h-10h; The ball milling is performed under an inert atmosphere or vacuum conditions.
12. The preparation method according to claim 8, characterized in that: In the diffusion alloy raw material, 6≤m'≤14, 24≤n'≤31, 30.7≤o'≤53.4, and 16≤p'≤23.
13. The preparation method according to claim 8, characterized in that: The mass content of the modified graphene in the grain boundary diffusion material is 10%-23%; The mass content of the graphene in the modified graphene is 19%-38%.
14. The preparation method according to claim 8, characterized in that: The ratio of the mass of the second main phase alloy raw material to the sum of the mass of the first main phase alloy raw material and the second main phase alloy raw material is 50%-69%; The ratio of the mass of the grain boundary phase alloy raw material to the sum of the mass of the first main phase alloy raw material, the second main phase alloy raw material and the grain boundary phase alloy raw material is 5%-17%.
15. The preparation method according to claim 8, characterized in that: The magnetic field orientation pressing molding comprises processing under a magnetic field of 1.5T-3.5T and a pressure of 170MPa-210MPa for 60s-150s; The sintering includes treating at 1030°C-1090°C for 4h-5.5h; The hot pressing includes a temperature of 550°C-800°C, 80MPa-150MPa and a vacuum degree of 10 -3 Pa-10 -2 Treat for 30min-150min under Pa conditions; The diffusion treatment includes heating at 600°C-1000°C and vacuum degree 10 -5 Pa-10 -2 Treat under Pa conditions for 2h-12h; The tempering treatment includes heating at 400°C-600°C and vacuum degree 10 -5 Pa-10 -2 Treat under Pa conditions for 2.5h-10h.
16. The preparation method according to claim 8, characterized in that: The sintering process also includes a pre-tempering treatment, which includes a treatment at 890° C.-950° C. for 2.5 h-5 h, and then a treatment at 480° C.-520° C. for 3.5 h-8 h.
17. A motor, characterized in that: The invention comprises the rare earth permanent magnet described in any one of claims 1 to 7 or the rare earth permanent magnet prepared by the preparation method described in any one of claims 8 to 16.
Citation Information
Patent Citations
Method for preparing crystal boundary nano-composite intensified neodymium iron boron magnet
CN103646777A
High-strength neodymium iron boron permanent magnet material
CN108417336A
High-coercivity rare earth permanent magnet and preparation method thereof
CN112071543A
Rare earth permanent magnet and preparation method thereof
CN112447350A
Graphene rare earth permanent magnet material and preparation method thereof
CN113053606A
